Simulating the PM2.5 in southern Taiwan under high-pressure return flow during the Kao-Ping Experiment (KPEx) - Ming-Tung Chuang; Charles C.K. Chou; Chuan-Yao Lin; Wei-Che Lin; Neng-Huei Lin; Wei-Nai Chen; Steven Soon-Kai Kong (Atmospheric Research, 2027)

Tuning oxidizing, reducing, and redox characteristics via Fe, Co, and Ni incorporation in Pd-based halloysite-supported bimetallic core–shell three-way catalysts - Yun-Ting Wang; Wei-Jing Li; Yu-Hao Lin; Ming-Yen Wey; Kui-Hao Chuang (Fuel, 2026)

MiR-4327 targets TP53 to promote cervical cancer cell proliferation - Mei-Lin Chen; Chen-Yang Chu; Feng-Xian Zhang; Li-Pei Zhang; Ying Yang; Bai-Zhao Peng; Chuang-Hai Wu; Xiao-Mei Chen; Yan-Ting You; Bing-Ying Rong; Hiu Yee Kwan; Xiao-Shan Zhao; et al. (Functional & Integrative Genomics, 2026)
Cervical cancer is a leading cause of female malignancy worldwide. While microRNA-4327 (miR-4327) has been implicated as a potential oncogene, its functional role and molecular mechanisms in cervical cancer pathogenesis remain unclear. This study aimed to determine the oncogenic function of miR-4327 and elucidate its downstream regulatory mechanism in cervical cancer pathogenesis. We measured miR-4327 expression in clinical cervical cancer tissues and cell lines using quantitative real-time PCR (qRT-PCR). We then assessed its effects on proliferation, migration, invasion, and cell cycle progression through functional assays including cell counting kit-8 (CCK-8), colony formation, transwell, and flow cytometry. To evaluate tumor growth in vivo, we established a xenograft model in non-obese diabetic (NOD)-severe combined immune-deficient (scid) mice. Using bioinformatic analysis and luciferase reporter assays, we identified TP53 as a direct target of miR-4327 and further validated this regulatory relationship with gain- and loss-of-function experiments. We found that miR-4327 was significantly upregulated in cervical cancer and promoted malignant phenotypes such as proliferation, migration, invasion, and cell cycle progression in vitro. Consistent with this, overexpression of miR-4327 accelerated tumor growth in vivo. Mechanistically, we confirmed TP53 as a direct functional target of miR-4327. Knocking down TP53 phenocopied the oncogenic effects of miR-4327, while restoring TP53 expression rescued the tumor-promoting effects mediated by miR-4327. These findings reveal a novel miR-4327/TP53 regulatory axis and nominate miR-4327 as a potential therapeutic target for intervention.

Melatonin attenuates gentamicin-induced cochlear hair cell injury by modulating the cGAS–STING signaling pathway - Han-gui Lu; Shuang-le Wang; Guo-feng Wen; Chuang-wei Li; Xin-sheng Lin (Tissue and Cell, 2026)

A dual mechanical tuning framework for rigid pillared elastic metamaterials: Geometric reconfiguration and controllable prestress - Zu Shao; Tong Cheng; Yi Zhang; Wei Zhong Jiang; Zhu Kun Mi; Xiang Jie Wei; Xin Guo; Wang Lin Xiong; Kai Hao Lin; Chuang Li; Shu Hao Song; Cheng Shen; et al. (Engineering Structures, 2026)

PBG-WaveNet: Probabilistic buoy-to-grid reconstruction and forecasting of significant wave height fields from sparse buoy observations - Nan Wang; Shangfei Lin; Chuang Liu; Mukun Chen; Zaijin You (Ocean Engineering, 2026)

Engineering bimetallic Cobalt–Iron glycerate Co-Catalysts on bismuth vanadate for improved charge transfer and photoelectrochemical catalytic water oxidation - Tsung-Rong Kuo; He-Jin Li; Kai-Jie Chuang; Chutima Kongvarhodom; Sibidou Yougbaré; Muhammad Saukani; Hung-Ming Chen; Lu-Yin Lin (Fuel, 2026)

Multidimensional analysis of pathogen epidemic patterns, their correlation with milk quality, and drug resistance and virulence traits of dominant pathogenic Escherichia coli in high-somatic-cell buffalo milk: Guangxi, China - Yifei Xiang; Zhifei Wei; Xuelian Mo; Yuying Liao; Chongli Wen; Mengyao Liao; Jiazhou Wei; Changhua Lin; Wenjing Li; Jiaji Chen; Lei Xu; Min Zhu; et al. (Food Microbiology, 2026)

Evolution of multiscale pore structure in saturated silty clay under non-coaxial F-T cycles - Chuang Lin; Jiahao Zhang; Han Zhao; Ke Yin; Feng Zhang; Decheng Feng (Engineering Geology, 2026)

Optimization of OARO-RO hybrid systems for the ammonium nitrogen recovery for wastewater treatment using an explainable machine learning - Xiao Xu; Jian Zhang; Chuang Li; Zhaohuan Mai; Liheng Dai; Erda Deng; Kecheng Guan; Pengfei Zhang; Kazuo Kumagai; Susumu Hasegawa; Yuqing Lin; Keizo Nakagawa; et al. (Desalination, 2026)

A chitosan-based cinnamaldehyde–raspberry ketone integrated carrier architecture for oral delivery toward mild metabolic regulation - Yu-Chi Wang; Sin-Huei Chuang; Chien-Fu Lin; Yan-Ting Lin; You-Song Cheng; Chih-Chen Lin; Chi-Chen Ting; Wei-Han Chen; Ting-Yu Chen; Shen-Ho Kuo; Fu-I Tung; Tse-Ying Liu (Carbohydrate Polymers, 2026)

Fine-scale mapping of built-environment carbon emissions: A multi-source data fusion and explainable machine learning framework for high-density urban regions - Ge Shi; Haoran Tang; Wei Wang; Chuang Chen; Jiantao Shi; Bo Wang; Lin Sun (Building and Environment, 2026)

Model test study of polyurethane grouting repair for gas pipelines in mining subsidence areas - Du Zibo; Tian Haodong; Ma Zhanguo; Li Lin; Zhang Jingwei; Zhou Chuang (Tunnelling and Underground Space Technology, 2026)

Greenwater due to plunging breaking wave impingement on a deck structure. Part 2: Impact pressure and air fraction - Meng-Chang Hsieh; Wei-Liang Chuang; Ting-Chieh Lin (Ocean Engineering, 2026)

Anthraquinone‑modulated oxygen disproportionation enables highly selective singlet oxygen generation for pollutant degradation - Yu Luo; Chenqi Lu; Chuang Xiao; Lin Ding; Mengyuan Zhao; Lingling Liu; Longshuai Zhang; Xibao Li; Fang Deng; Xubiao Luo; Jian-Ping Zou (Journal of Environmental Chemical Engineering, 2026)

Early microbial succession and matrix destabilization guide long-term preservation of refrigerated kelp - Neng-Pai Shi; Si-Chuang Tu; Bing-Bing Wu; Ru-Meng Xiao; Hai-Bin Pan; Sheng-Nan Lin; Roger Ruan; Xue-Mei Hou; Xiang-Yang Lin (Food Chemistry, 2026)

Poly(lactic-co-glycolic acid) (PLGA)-based vaccine delivery systems for fish: physicochemical properties, immunological mechanisms, and applications - Shu-Chun Chuang; Yi-Chen Lin; Ya-Shuan Chou; Shang-Pin Liu; Shao-Wen Hung; Ti-Chun Chang; Chung-Hwan Chen; Chung-Da Yang (Fish & Shellfish Immunology, 2026)

First biomonitoring of micro/nanoplastic pollution in freshwater fish from Yalong River, China: accumulation dynamics, influencing factors and ecological risk - Mingpeng Zheng; Minmin Xie; Xinglian Lin; Shipeng Zhou; Yixuan Chen; Pinpin Zhang; Zhaobin Song; Chuang Zhou (Environmental Research, 2026)

Functional polysaccharide-based bioactive delivery systems for urinary and reproductive system therapeutics - Yung-Wei Lin; Lekshmi Rethi; Wen-Yu Pan; Hieu Trung Nguyen; Andrew E.-Y. Chuang (Drug Delivery and Translational Research, 2026)

Microbial-derived metabolites coordinate growth regulation and stress tolerance in Phalaenopsis orchids - Nur Izzatul Maulidah; I-Hung Lin; Yun-Teng Yen; Ting-Yu Liou; Huey-wen Chuang (Journal of Plant Physiology, 2026)

Atmospheric new particle formation from sulfuric acid-amine nucleation in a rural area of the North China Plain - Yiliang Liu; Yiqun Lu; Gan Yang; Chuang Li; Yuwei Wang; Runlong Cai; Lei Yao; Yang Chen; Lin Wang (Journal of Environmental Sciences, 2026)

Deep learning inversion of electrical resistivity tomography using an enhanced U-Net for mapping discontinuous permafrost - Tianci Liu; Yahui Du; Chuang Lin; Bo Tian; Decheng Feng; Feng Zhang (Journal of Applied Geophysics, 2026)

Westerly reorganization driven by orbital forcing: Late Miocene aridification in the Tarim Basin, Central Asia - Dong Wang; Qingqing Qiao; Chuang Xuan; Zhuangzhuang Lv; Sunyi Dong; Gangqiang Li; Long Ma; Yudong Chen; Zhanwei Lin; Zhongyin Gao (Global and Planetary Change, 2026)

The empowerment path of corporate carbon performance by executive environmental background - Liping Wang; Shanyu Lin; Qianwen Ma; Chuang Li (Environment, Development and Sustainability, 2026)

First complete coding sequence of ovine herpesvirus 2 from a malignant catarrhal fever case of Formosan sambar deer in Taiwan: Genomic characterization and molecular epidemiology - Ruei-Sheng Tsai; Shih-Te Chuang; Hau-You Tzeng; Fong-Yuan Lin; Ching-Yu Tseng; Yi-Chen Chen; Wei-Li Hsu (The Veterinary Journal, 2026)

Interrelationships among PM2.5/O3 concentrations, polluted weather patterns, and meteorological conditions over Taiwan based on 2006–2024 observations - Ming-Tung Chuang; Charles C.-K. Chou; Chuan-Yao Lin; Wei-Che Lin; Meng-Hsuan Lee; Ja-Huai Lee; Chih-Chung Chang; Wei-Nai Chen; Chian-Yi Liu (Atmospheric Research, 2026)

Robust optimal control for reconfiguration of Coulomb spacecraft formations along invariant manifolds - Peerawat Artitthang; Chuang Yao; Mingpei Lin (Advances in Space Research, 2026)

Dang-Gui-Bu-Xue-Tang triggers GM-CSF and IL-4 secretion corporated with increased amount of Immunoglobulins - Sheng-Teng Huang; Jia-Hau Yen; Yu-Chun Lin; Ming-Ching Kao; Chia-Ju Chuang; Shu-Tuan Chiang; Te-Mao Li (Advances in Traditional Medicine, 2026)

Single-cell transcriptomics reveal PRRC1 as a malignant cell enriched driver of DNA repair and therapy resistance in glioblastoma - Sachin Kumar; Ming-Cheng Tsai; Dahlak Daniel Solomon; Juan Lorell Ngadio; Do Thi Minh Xuan; Ching-Chung Ko; Hung-Yun Lin; Meng-Chi Yen; I-Jeng Yeh; Yung-Kuo Lee; Hui-Ru Lin; Jian-Ying Chuang; et al. (DNA Repair, 2026)

Applying the iRIC Morpho2DH model to determine the effectiveness of check dams against debris flows - Zheng-Yi Feng; Philipp Marr; Tien-Chun Hsu; Ping-Hsuan Kuo; Yu-Po Lin; Ming-Chih Chuang; Ching-Mao Huang; Edoardo Carraro; Su-Chin Chen; Chen-Yu Chen; Thomas Glade (Landslides, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Data-driven assessment of nitrogen and phosphorus buffering capacity across 460 Chinese watersheds: Spatial patterns, drivers, and future projections - Yunfei Cao; He Yao; Chuang Zhang; Chaojun Gu; Lin Yang; Rui Hao; Xiao Li; Zhen Wang; Haibing Xiao; Jian Wang; Zhihua Shi (Water Research, 2026)

Waste lignin-based N/O-rich carbon nanofibers as bifunctional materials for efficient CO2 conversion and energy storage - Wei Hui; Xin Wang; Zao-Lin Hu; Ming-Yu Zhao; Jia-Xin Feng; Wen Chen; Xiao-Yu Xiao; Chuang-Qi Zheng; Lei Pu (Journal of Environmental Chemical Engineering, 2026)

Drainage performance for clay slopes with wicking tubes in seasonally frozen regions: Experiment and field monitoring - Zhimin Ma; Chuang Lin; Guanfu Wang; Decheng Feng; Feng Zhang (Geotextiles and Geomembranes, 2026)

Chlorine-resistant high-entropy spinel oxide catalyst for efficient and durable seawater anion exchange membrane water electrolysis - Thi Xuyen Nguyen; Ting-You Shih; Ngoc Thanh Thuy Tran; Thanh Tuan Nguyen; Yi-Chuan Chu; Bo-Han Lai; Chun-Kuo Peng; Yu-Ru Lin; Yan-Gu Lin; Kao-Shu Chuang; Jeng-Kuei Chang; Thi Y Phung Nguyen; et al. (Chemical Engineering Journal, 2026)

Zebrafish Model Reveals Early Electrocardiographic and Molecular Signatures of Doxorubicin-Induced Cardiotoxicity - Zih-Yin Lai; Chi-Ying Lee; Yu-Ching Chiu; Chia-Hung Lin; Chung-Chi Yang; Chia-Chia Ho; Lawrence Yu-Min Liu; Yung-Jen Chuang (Cardiovascular Toxicology, 2026)

Experimental investigation of impact pressures and air entrainment effects during flat plate water entry at varying impact speeds and aeration levels - Sheng-Mei Lin; Wei-Liang Chuang (Ocean Engineering, 2026)

Cellular vesicle–electrically conducting polymer integrating with microalgae attenuate retinal inflammation associated with IL-6, immunomodulation, and pro-inflammatory cytokines in diabetes-related retinal disease - Andrew E.-Y. Chuang; Yo-Lin Chen; Chia-Hung Liu; Hieu Trung Nguyen; Tsung-Jen Wang; I-Chan Lin (Chemical Engineering Journal, 2026)

An overview of GNSS for tsunami early warning: From lithosphere to ionosphere - Kejie Chen; Haishan Chai; Jiafeng Li; Guoguang Wei; Mingzhe Lyu; Wenfeng Cui; Chuang Shi; Linlin Li; Peitao Wang; Wei Lu; Jian Lin (Science China Earth Sciences, 2026)

Role of ITIH4 in Modulating YAP/TAZ-Mediated Apoptosis of Type II Alveolar Epithelium during Acute Respiratory Distress Syndrome - Yu-Syuan Shih; Xiao-Yue Chen; Yi-Wei Lin; Zih-An Liao; Yi-Hsuan Liu; Vincent Laiman; Syue-Wei Peng; Kazuhiro Ito; Hsiao-Chi Chuang (Pharmaceutical Research, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Pyrolysis atmosphere dictates the efficacy of peanut shell biochar in promoting anaerobic digestion of chicken manure - Tingting Zhang; Xiaohong Su; Xinrui Xu; Ruian Lin; Hongmei You; Yupeng Wang; Chuang Zhou (Journal of Environmental Chemical Engineering, 2026)

Sonofoam: An ultrasound-responsive foam for broad pleural coverage and sonoporation-enhanced drug delivery in pleurodesis - Hsin-Yi Lin; Wei-Chih Liao; Yun-Chieh Lin; Hsin-Chin Li; Min-Yu Tsou; Bo-Tai Cheng; Yu-Nan Huang; Ulziijargal Sukhbat; Chun-Yi Chiang; Chi-Fen Chuang; Zong-Han Hsieh; Chih-Yen Tu; et al. (Chemical Engineering Journal, 2026)

NeuProIO: A dual-action solid drug nanoparticle topical formulation for simultaneous intraocular pressure reduction and neuroprotection for glaucoma - Lei Xu; Mu Li; Lin Qi; Tzu-Chen Wang; Dong Liu; Vimalin Jeyalatha Mani; Hsin-Yin Chuang; Qingbo Yang; Ruipu Mu; Samira Mahdi; Da Huang; Honglan Shi; et al. (Chemical Engineering Journal, 2026)

Modified QuEChERS coupled with hybrid mass spectrometry for 322 target pesticides and suspect screening of emerging organic contaminants in agricultural soils - Yu-Hui Chang; Chi-Chieh Hu; Chinn-Yuan Fu; Sichao Wang; Yu-Min Tzou; Shiou-Ruei Lin; Hsiao-Ying Yang; Jerry J. Wu; Cheng-Hua Liu; Ya-Hui Chuang (Journal of Hazardous Materials, 2026)

Five-birds-with-one-stone: Employing novel sucrose derived carbon dots to modify cementitious materials - Haijie He; Xiangzhi Wang; Yangrui Wang; Haoming Gao; Jing Zhang; Caiyuan Lin; Yuan Fang; Chuang He; Bin Wang (Journal of Cleaner Production, 2026)

Crab bioturbation enhanced sediment nitrogen retention and weakened N2O production in saline-alkaline paddies - Xinru Zeng; Xianbiao Lin; Can Wang; Hongwei Shan; Chuang Sun; Fang Wang (CATENA, 2026)

Diagenesis and burial history controls on Oligocene Huagang sandstones, southern Xihu Sag (East China Sea Basin): Implications for the formation of effective reservoirs - Hong-Liang Huo; Cheng-Lin Liu; Dao-Wu Huang; An-Qi Tian; Rizwan Sarwar Awan; Hong-Yan Gao; Chuang-Xin Liu; Xue-Yong Chen; Zi-Ye Tian; Tao-Zheng Yang; Bin-Bin Liu; Chao-Jun Liang (Marine and Petroleum Geology, 2025)

Tailoring nickel glycerate electrodes through precursor chemistry and sulfurization for enhanced battery-supercapacitor hybrid performance - Tsung-Rong Kuo; Yun-Hsi Wang; Bo-Yang Chuang; Chutima Kongvarhodom; Sibidou Yougbaré; Muhammad Saukani; Hung-Ming Chen; Lu-Yin Lin (Journal of Environmental Chemical Engineering, 2025)

Low-temperature heat recovery: An economic approach to renovate air-impaired LiNbOCl4 electrolyte for boosted stability in high-performance all-solid-state batteries - Lin Li; Shiyu Liu; Siwu Li; Ziling Jiang; Qiyue Luo; Ziyu Lu; Miao Deng; Wenqian Tian; Jie Yang; Chen Liu; Qiao Wang; Chuang Yu (Chemical Engineering Journal, 2025)

Thiocyanate-improved deep eutectic solvent electrolyte for cathode-free FeLi dual-ion batteries - Krishnakumar Melethil; Tsung-Wu Lin; Wei-Tao Peng; Min-Chieh Chuang; Zdenek Sofer; Jeng-Yu Lin (Chemical Engineering Journal, 2025)

Research on the Characteristics of Deep and Medium-Level Geothermal Energy for Highway Ice Melting and Snow Removal - Taking the Jinan-Ningjin Expressway as an Example - Chuang-shan Wu; Zhao-di Han; Wen-xiang Yang; Jing-kai Qu; Zhao-feng Zheng; Fan-meng Kong; Kun Liang; Lin-zhi Lang (Applied Geophysics, 2025)

Linking source-to-sink processes, organic matter composition, and oxygen consumption on a shallow passive margin shelf sustained by small mountainous rivers - Yu-Shih Lin; Chih-Lin Wei; Yuan-Pin Chang; Jih-Terng Wang; Shu-Ying Chuang; Liang-Chi Wang; James T. Liu; Hong-Chun Li; Chieh-Wei Hsu (Geochimica et Cosmochimica Acta, 2025)

Controllable growth of halide electrolyte crystal planes enables superior cycling stability of high-voltage all-solid-state batteries - Qiyue Luo; Siwu Li; Lin Li; Ziling Jiang; Ziyu Lu; Wenwen Hu; Miao Deng; Jie Yang; Zhenyu Wang; Chen Liu; Chuang Yu (Chemical Engineering Journal, 2025)

Shear behavior of precast pile-soil interface in warm permafrost regions - Guanfu Wang; Linhui Lu; Liam Wotherspoon; Chuang Lin; Bo Tian; Decheng Feng; Feng Zhang (Cold Regions Science and Technology, 2025)

A neutral multivalent AIE–TICT scaffold: An off-on, wash-free fluorogenic strategy for biosensing glycan–protein interactions in live cells and mycobacteria - Huai-En Chang; Chien-Chin Chen; Yi-Jin You; Pei-Hsuan Lee; Bo-Chang Ruan; Hong-Luen Kwok; Ching-Tse Wu; Chuang-Rung Chang; Jiun-Han Chen; Eugene C. Lin; Pei-Jhen Li (Analytica Chimica Acta, 2025)

Phytochemical analysis and quality control study of Dendrobium fimbriatum Hook. Flowers - Anham Abbasi; Yuan-Shiun Chang; Wu-Chang Chuang; Hung-Rong Yen; Michael Heinrich; Chia-Lin Lee (Phytochemistry Letters, 2025)

Characteristics of atmospheric reduced-sulfur compounds at a suburban site of Shanghai - Kai Deng; Juntao Huo; Yuwei Wang; Lihong Wang; Sijia Yin; Chuang Li; Yueyang Li; Gan Yang; Lei Yao; Qingyan Fu; Lin Wang (Journal of Environmental Sciences, 2025)

Ion/electron/stress-triple-regulated Li deposition via multifunctional bismuth species in sulfide-based all-solid-state lithium metal batteries - Ziling Jiang; Siwu Li; Wenwen Hu; Shiyu Liu; Lin Li; Jie Yang; Miao Deng; Ziyu Lu; Xinxin Wang; Qin Chen; Hui Yang; Chen Liu; et al. (Chemical Engineering Journal, 2025)

Low-intensity pulsed ultrasound enhances delivery of 30 nm Q10 for improving mental and memory disorder in APP/PS1 mice - Qi Luo; Xuanjie Ye; Jinan Xu; Zihui Sun; Panpan Wang; Haishu Chen; Tingting Gao; Qiangfeng Deng; Ziwen Wang; Qin Wang; Xiaoxiao Chen; Zhuowen Zhao; et al. (Drug Delivery and Translational Research, 2025)

Development and characterization of a high-resolution, high-sensitivity collinear resonance ionization spectroscopy system - Han-Rui Hu; Yang-Fan Guo; Xiao-Fei Yang; Zhou Yan; Wen-Cong Mei; Shao-Jie Chen; Yin-Shen Liu; Peng Zhang; Shi-Wei Bai; Dong-Yang Chen; Yong-Chao Liu; Shu-Jing Wang; et al. (Science Bulletin, 2025)

Analysis of spontaneous failure of lithium-ion battery under micromechanical deformation - Chuang Qi; Hongtao Yan; Hao Cheng; Yuemeng Zhang; Chunjing Lin; Siqi Chen; Xi Liu; Li Lao; Yazhou Sun; Qiang Wang (Process Safety and Environmental Protection, 2025)

Coffee mitigated cognitive impairments in sleep-deprived mice by regulating circadian rhythm, inflammation, oxidative stress, and intestinal ecology - Hui-Bin Jiang; Fen-Fen Wei; Wen-Ting Li; Zi-Han Lin; Chuang Zhu; Yan Wu; Ying Wang; Li-Hua Song (Food Bioscience, 2025)

Fate, transport, and plant uptake of ricinine in soils amended with castor cake organic fertilizer - Ya-Hui Chuang; Kai-Xuan Zheng; Siu Chun Wong; Yu-Min Tzou; Sichao Wang; Shiou-Ruei Lin; Hsiao-Ying Yang; Chinn-Yuan Fu; Jerry J. Wu; Cheng-Hua Liu (Journal of Hazardous Materials, 2025)

Three types of extreme cold events over East Asia and the associated atmospheric circulations - Chuang Zheng; Lin Wang; Yuyun Liu; Zizhen Dong (Climate Dynamics, 2025)

All-in-one and on-demand wound dressing based on a deep eutectic solvent ionic gel - Jia-Yu Yang; Yu-Lin Tsai; Ting-Hui Cheng; Yu-Lin Su; Yi-Kai Hong; Yu-Chen Lin; Da-Huei Lee; Chao-Chun Yang; Chao-Kai Hsu; Li-Chieh Kuo; Cheng-Hsin Chuang (Chemical Engineering Journal, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Accelerated oxidation behaviors and thermodynamic characteristics of unburned gangue for road applications - Deng Ma; Chuang Lin; Feng Zhang; Yonggang Duan; Decheng Feng (Fuel, 2025)

Accelerated detection of carbapenem resistance in Klebsiella pneumoniae via single-cell Raman spectroscopy - Jia-Cheng Ding; Li-Ting Dai; Jia-Xin Tang; Hui-Min Zhang; Le-Le Zhai; Chuang-Ye Cai; Zhi-Rou Xiao; Zhe-Mei Chen; Jia-Hui Ling; Meng-Xue Zou; Xi-Wu Cao; Li-Juan Lin; et al. (World Journal of Microbiology and Biotechnology, 2025)

Correlation between the utilization of sodium-glucose cotransporter-2 (SGLT2) inhibitors and the risk of dementia: a nationwide population-based study in Taiwan - Wu-Lung Chuang; Stella Chin-Shaw Tsai; Yi-Chun Yang; Tsai-Ling Hsieh; Heng-Jun Lin; Yu-Han Huang; Fuu-Jen Tsai; Kuang-Hsi Chang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

ONC201 exerts oncogenic effects beyond its mitochondria-disturbing role in neuroblastoma subsets - Jyun-Hong Jiang; Yu-Han Lin; Pei-Lin Liao; Ting-Ya Chen; Hui-Ching Chuang; Chao-Cheng Huang; Wen-Ming Hsu; Jiin-Haur Chuang; Wei-Shiung Lian (Journal of Molecular Medicine, 2025)
Neuroblastoma (NB) is a formidable challenge in pediatric oncology due to its intricate molecular landscape, necessitating multifaceted therapeutic approaches. ONC201 is an imipridone antibiotic compound with a promising drug candidate leveraging its potent anticancer properties against the mitochondrial proteases ClpP and ClpX. Despite demonstrating early clinical promise, particularly in MYCN -amplified NB, its efficacy in non- MYCN -amplified NB remains a subject worthy of investigation. In this study, we extended the coverage of ONC201 to treat non- MYCN -amplified NB, and our data implicated ONC201’s inability to reduce tumor growth in animal models harboring SK-N-AS or SK-N-FI cell lines. Interestingly, ONC201 induced the expression of oncogenic markers c-Myc and LGR5 while downregulating the tumor suppressor ATRX. While it fails to attenuate tumor neovascularization in non- MYCN -amplified NB xenografts, its effectiveness differs from that of its MYCN-amplified counterpart. Rho zero (ρ0)-SK-N-AS cells treated with ONC201 showed comparable observed trends in parental SK-N-AS cells, including LGR5 upregulation and ATRX downregulation, suggesting that ONC201’s multifaceted actions extend beyond mitochondrial targets. Our elucidation highlights the need to discern molecular signatures when deploying ONC201 monotherapy against NB, which lacks MYCN- amplification.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Surveillance and genetic diversity of bovine viral diarrhea virus in dairy herds across Taiwan - Fong-Yuan Lin; Hau-You Tzeng; Ching-Yu Tseng; Ruei-Sheng Tsai; Mami Oba; Tetsuya Mizutani; Yumiko Yamada; Hue-Ying Chiou; Shih-Te Chuang; Wei-Li Hsu (The Veterinary Journal, 2025)

The significance of slowly biodegradable COD on denitrification in the OAO process - Tzu-Chuan Lin; You-Ren Yang; Quoc Khanh Nguyen; Ming-Chi Chiu; Hui-Min Yen; Kao-Hsiao Chen; Shun-Hsing Chuang (Journal of Environmental Management, 2025)

Integrative analyzing the molecular basis of Clerodendranthus spicatus aqueous extract in hyperuricemia nephropathy via network pharmacology and experimental validation - Chuang Li; Danyao Lin; Jianting Ouyang; Junyi Liu; Shouhai Wu; Delun Li; Fan Yang; Haohao Quan; Yimeng Li; Qiaoru Wu; Guirui Huang; Wei Mao (Food Bioscience, 2025)

A formula of quantile of extreme wind pressure coefficient to estimate wind load with various mean recurrence intervals - Lin Da; Qingshan Yang; Min Liu; Ke Zhou; Chuang Li (Engineering Structures, 2025)

Impact of Coal-Fired Power Plants on Suspended Sediment Concentrations in Coastal Waters - Zhi-Cheng Huang; Po-Chien Lin; Po-Hsun Lin; Shun-Hsing Chuang (Journal of Marine Science and Engineering, 2025)
Many coastal coal-fired power plants utilize seawater flue gas desulfurization (SWFGD) systems, which may pose risks of heavy metal attachment on suspended sediments. Understanding variations in suspended sediment concentration (SSC) is therefore useful for controlling marine pollution. We studied two power plants as examples of discharging SSC using continuous measurement techniques. Monitoring sites at intake and discharge points and the surrounding coastal areas of the power plants was conducted across seasons. The first case study, Linkou Power Plant, is located in a high-SSC region influenced by monsoon winds and wave activity. Results indicate that SSC levels at all the monitoring sites are correlated with environmental factors of wind and wave conditions, with strong positive correlations observed between the intake and discharge points. In contrast, the Dalin Power Plant is located within an international harbor, where the SSC levels are generally low; however, sudden increases in SSC are observed at the intake point due to disturbances from vessel activities. These sudden increases are not evident at the discharge point, suggesting a sink of SSC may occur within the system. These results demonstrate that the two studied power plants have limited effects on the increase in SSC; the SSC in the discharge point is mainly related to the SSC input at the intake point. Effective management of SSC at the intake may help mitigate coastal pollution caused by SSC discharge and reduce the risk of harmful substances adhering to suspended solids in the discharging wastewater.

Insertional mutagenesis of AIDA or CYP720B1 in the green alga Chlamydomonas reinhardtii confers copper(II) tolerance and increased biomass - Ya Li; Lin Jiang; Chuang Xu; Suhui Wang; Yunyao Qian; Yiqiong Wu; Chenyu Miao; Zhouzhou Dong; Liang Wang (Journal of Hazardous Materials, 2025)

Artificial digestion represents the worst-case scenario for studying nanoplastic fate in gastrointestinal tract - Giselle Lee; Ya-Jhu Jhang; Yu-Tung Jhang; Yen-Chen Chang; Hui-Wen Chang; Chun-Yu Chuang; Yung-Kun Chuang; Ching-Wei Lin; I-Lun Hsiao (Journal of Hazardous Materials, 2025)

Modifying pea protein by cold plasma for the development of functional vegan cheese - Bing-Fan Chuang; Sheng-Yi Chen; Jer-An Lin; Gow-Chin Yen (Food Bioscience, 2025)

Experimental study on shear behavior of geotextile encased lime energy column - soil interface in degraded permafrost environment - Guanfu Wang; Lei Zhou; Chuang Lin; Zhichao Liang; Decheng Feng; Feng Zhang (Cold Regions Science and Technology, 2025)

Insight into the plasma-catalyst removal process of CH4-NOx under marine LNG engine exhaust conditions: Experiment and chemical kinetics - Chuang Xiang; Lin Lyu; Junjie Liang; Neng Zhu (Process Safety and Environmental Protection, 2025)

The obesity-related mutation gene on nonalcoholic fatty liver disease - Yen-Yu Chen; Chi-Sheng Chen; Jee-Fu Huang; Wen-Hsiu Su; Chia-Yang Li; Wei-Shiun Chen; En-Sheng Lin; Wan-Long Chuang; Ming-Lung Yu; Shu-Chi Wang (Human Genetics, 2025)

Fecal microbiota transplantation as an effective way in treating methylmercury-poisoned rats - Yanfei Zhang; Qingxuan Liu; Hongxin Xie; Wei Zhang; Xiaoying Lin; Huifeng Zhang; Huan Yu; Yinghui Ma; Chuang Zhang; Hao Geng; Nianqiu Shi; Liwei Cui; et al. (Science of The Total Environment, 2024)

Isolation and screening of high biofilm producing lactic acid bacteria, and exploration of its effects on the microbial hazard in corn straw silage - Chuang Yang; Binhong Huang; Jinhong Lin; Qijing Yang; Yongqing Guo; Dewu Liu; Baoli Sun (Journal of Hazardous Materials, 2024)

Screening and safety assessment of migrating substances released from biodegradable packaging materials into milk - Chuang-Chuang Zhao; Qin-Bao Lin; Cang-Hao Xie; Yi-Qi Liu; Huai-Ning Zhong; Wei-Yue Gu; David Julian McClements; Da Ma (Food Control, 2024)

Aluminate-activated nano-SiO2 for enhancing water vapor barrier properties in polymers films: A safe and effective strategy - Chuang-Chuang Zhao; Qin-Bao Lin; Yan-Fen Chen; Huai-Ning Zhong; David Julian McClements; Da Ma (Food Packaging and Shelf Life, 2024)

The association of air pollution with blood pressure, heart rate and stress among office workers using essential oils - Chien-Yu Lee; I-Jung Liu; Chih-Hong Pan; Lian-Yu Lin; Hsiao-Chi Chuang; Kin-Fai Ho; Chia-Huang Chang; Kai-Jen Chuang (Atmospheric Environment, 2024)

PM2.5 episodes in northern Taiwan under southerly winds in late winter - Ming-Tung Chuang; Charles C.-K. Chou; Chuan-Yao Lin; Ja-Huai Lee; Wei-Che Lin; Meng-Hsuan Li; Shyh-Wei Chen; Shu-Hao Chang (Atmospheric Research, 2024)

Source apportionment of PM2.5 episodes in the Taichung metropolitan area, Taiwan - Ming-Tung Chuang; Charles C.-K. Chou; Chuan-Yao Lin; Wei-Che Lin; Ja-Huai Lee; Meng-Hsuan Li; Wei-Nai Chen; Chih-Chung Chang; Chian-Yi Liu; Yi-Chun Chen (Atmospheric Research, 2024)

Dynamic Response Assessment of Floating Offshore Wind Turbine Mooring Systems with Different In-Line Tensioner Configurations Based on Fully Coupled Load Calculations - Wenhua Li; Guanlin Du; Shanying Lin; Zhenju Chuang; Fei Wang (Journal of Marine Science and Engineering, 2024)
In-line tensioning technology has significantly reduced the cost barriers that previously hindered the expansion of the floating offshore wind industry. However, assessing the impact of in-line tensioners on the dynamic response of floating offshore wind turbines (FOWTs) lacks effectiveness, and the relevant mooring configuration specifications are not complete. Thus, a fully coupled calculation method is introduced in this paper to solve the relevant issues in mooring systems with in-line tensioners using a classic spar platform model. Three distinct design scenarios were selected to study the variation in mooring configurations of in-line tensioners along different mooring lines and at varied positions within each line. The potential occurrence of reverse tension phenomena was deliberated and assessed. We identified the varying tension patterns at the fairlead and in-line tensioner locations in mooring systems with in-line tensioners, and the influence of such variations on platform dynamics. The findings also demonstrate that the appropriate configuration of in-line tensioners should be selected to avoid the risk of reverse tension. This research has potential to contribute to the security and economy of the deployment of this emerging in-line mooring method.

Vision-based trajectory generation and tracking algorithm for maneuvering of a paddy field robot - Dengbin Fu; Zhiying Chen; Zhiqiang Yao; Zhanpeng Liang; Yinghu Cai; Chuang Liu; Zhenyu Tang; Caixia Lin; Xiao Feng; Long Qi (Computers and Electronics in Agriculture, 2024)

Tin-based dual-modification enabling enhanced air stability and electrochemical performance for Li5.5PS4.5Cl1.5 in all-solid-state lithium metal batteries - Jie Yang; Ziling Jiang; Chen Liu; Lin Li; Siwu Li; Zhongkai Wu; Chaochao Wei; Qiyue Luo; Long Zhang; Shijie Cheng; Chuang Yu (Chemical Engineering Journal, 2024)

Stabilization of single crystal LiNi0.90Mn0.05Co0.05O2 via ZrO2 dual-functional coating enables superior performance for solid-state lithium battery - Chen Liu; Qiyue Luo; Lin Li; Chaochao Wei; Siwu Li; Xia Li; Wanming Li; Zihan Zhang; Zhongkai Wu; Zilin Jiang; Hui Yang; Long Zhang; et al. (Chemical Engineering Journal, 2024)

On theoretical and practical analyses of BDS-3/Galileo/GPS all-in-view and PPP time transfer with the consideration of satellite clock biases - Dong Zhang; Fu Zheng; Meng Wang; Yuanhui Lin; Liangcheng Deng; Zhen Wang; Chuang Shi (Journal of Geodesy, 2024)

Soluble Epoxide Hydrolase Inhibitor Ameliorates Olfactory Dysfunction, Modulates Microglia Polarization, and Attenuates Neuroinflammation after Ischemic Brain Injury - Chien-Fu Yeh; Tung-Yueh Chuang; Ming-Ying Lan; Yung-Yang Lin; Wei-Hao Huang; Yu-Wen Hung (Journal of Neuroimmune Pharmacology, 2024)

Structure-Functional Activity of Pyrone Derivatives for Inhibition of Barnacle Settlement and Biofilm Formation - Mo Aqib Raza Khan; Bo-Wei Wang; Hsiu-Chin Lin; Yu-Liang Yang; Chih-Chuang Liaw (Marine Biotechnology, 2024)

Development of Quantitative Norms for Normal Lung Uptake Based on Three-Dimensional Gallium-67 Single Photon Emission Computed Tomography/Computed Tomography - Tzyy-Ling Chuang; Wei-Lin Li; Yu-Ching Hs; Jyh-Cheng Chen; Yuh-Feng Wang (Journal of Medical and Biological Engineering, 2024)
Purpose Gallium-67 (Ga-67) lung scans assess alveolitis and interstitial lung disease, with Ga-67 accumulation correlating with inflammation intensity as seen in lung biopsy sections. Both semi-quantitative and quantitative methods have been used, with the latter providing an inflammatory activity index linked to lung lavage and histopathological scores. However, differing reference points result in varying outcomes. This study aimed to establish standard Ga-67 index parameters using semi-quantitative analysis and a linear regression model based on planar and SPECT/CT images. Methods Twenty subjects without lung disease received a 5–6 mCi Ga-67 injection via the ankle. Both planar and SPECT/CT images were analyzed, with semi-quantitative values assessed using GraphPad Prism 9.5.1. Results Compared to planar images, SPECT/CT acquisitions for the lung-to-arm uptake ratio proved the most reliable indicator for assessing lung inflammation. Increased lung Ga-67 uptake was defined as greater than 2 standard deviations from the average Ga-67 uptake for healthy subjects. The normal range was 0.065 ± 0.049 for the right side and 0.076 ± 0.070 for the left side. Conclusion Lung-to-arm ratios in SPECT/CT images are more accurate than those in planar images. This method should be adopted as a standard clinical practice, providing more reliable diagnostic information and improving patient management. Future studies should compare patients without lung disease to those with lung disease to determine the diagnostic benefit of these norms.

Thermal runaway and gas production characteristics of semi-solid electrolyte and liquid electrolyte lithium-Ion batteries: A comparative study - Chunjing Lin; Hongtao Yan; Chuang Qi; Zhenyan Liu; Dinghong Liu; Xi Liu; Li Lao; Zhaoyang Li; Yazhou Sun (Process Safety and Environmental Protection, 2024)

Environmental pressure exerted by the petrochemical industry and urban environmental resilience: Evidence from Chinese petrochemical port cities - Chuang Tian; Yahui Liang; Qiaoqiao Lin; Dongni You; Zun Liu (Journal of Cleaner Production, 2024)

Biofunctionalized hydrogel composed of genipin-crosslinked gelatin/hyaluronic acid incorporated with lyophilized platelet-rich fibrin for segmental bone defect repair - Er-Yuan Chuang; Yi-Cheng Lin; Yu-Min Huang; Chih-Hwa Chen; Yi-Yen Yeh; Lekha Rethi; Yu-Jen Chou; Pei-Ru Jheng; Jen-Ming Lai; Chang-Jung Chiang; Chin-Chean Wong (Carbohydrate Polymers, 2024)

Discontinuous permafrost detection from neural network-ensemble learning based electrical resistivity tomography - Tianci Liu; Feng Zhang; Chuang Lin; Zhichao Liang; Guanfu Wang; Decheng Feng (Cold Regions Science and Technology, 2024)

Multicenter study on clinical outcomes and poor prognostic factors in patients with Klebsiella pneumoniae bacteremia receiving cefoperazone/sulbactam treatment - Tsung-Ta Chiang; Ming-Hsien Chiang; Hung-Jen Tang; Zhi-Yuan Shi; Mao-Wang Ho; Chia-Hui Chou; Shang-Yi Lin; Po-Liang Lu; Ting-Shu Wu; Shian-Sen Shie; Jien-Wei Liu; Feng-Yee Chang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Background Infections caused by Klebsiella pneumoniae are common and result in high mortality rates. In vitro studies demonstrated the potency of cefoperazone/sulbactam (CPZ/SUL) against Klebsiella pneumoniae . However, the clinical efficacy of CPZ/SUL for the treatment of K. pneumoniae bacteremia has not been studied. Objectives This study aimed to associate the clinical outcomes of patients with bacteremia with the minimal inhibitory concentrations (MICs) of CPZ/SUL against the causative K. pneumoniae isolates. Methods This multicenter, retrospective study was conducted in Taiwan between July 2017 and April 2021. Patients with K. pneumoniae bacteremia treated with CPZ/SUL were enrolled in this study. CPZ/SUL MICs were determined using the agar dilution method. Data on the patients’ clinical outcomes and characteristics were collected and analyzed. Results In total, 201 patients were enrolled. Among the causative K. pneumoniae isolates, 180 (89.5%) were susceptible to CPZ/SUL. Most patients ( n = 156, 77.6%) had favorable outcomes. The 30-day mortality rate was 11.9% ( n = 24). Multivariate risk analyses showed that higher APACHE II score (Odds Ratio [OR], 1.14; Confidence Interval [CI], 1.07–1.21; p < 0.001), metastatic tumors (OR, 5.76; CI, 2.31–14.40; p < 0.001), and causative K. pneumoniae CPZ/SUL MICs > 16 µg/ml (OR, 4.30; CI, 1.50–12.27; p = 0.006) were independently associated with unfavorable outcomes. Conclusion Patients with K. pneumoniae bacteremia treated with CPZ/SUL at a ratio 1:1 had favorable outcomes when the CPZ/SUL MICs were ≤ 16 µg/ml. Patients with higher APACHE II scores and metastatic tumors had unfavorable outcomes.

Improvement of the Diagnostic Method for the Detection of Parasite Eggs Using the Formalin Ethyl Acetate Concentration Technique - Jia-Hung Liou; Te-Ling Lu; Hui-Fen Cheng; Long-Wei Lin; Po-Cheng Kung; Hong-Jing Chuang; Te-Hsiu Lee; Chee-Hong Chan; Te-Jung Lu (Acta Parasitologica, 2024)

Elucidation of the beneficial role of co-fermented whole grain quinoa and black barley with Lactobacillus on rats fed a western-style diet via a multi-omics approach - Zi-Han Lin; Ling-Yue Zhong; Hui-Bin Jiang; Chuang Zhu; Fen-Fen Wei; Yan Wu; Li-Hua Song (Food Research International, 2024)

Spatiotemporal characterization of PM2.5, O3, and trace gases associated with East Asian continental outflows via drone sounding - Chih-Yuan Chang; Jia-Lin Wang; Yen-Chen Chen; Wei-Nai Chen; Sheng-Hsiang Wang; Ming-Tung Chuang; Neng-Huei Lin; Charles C.-K. Chou; Wei-Syun Huang; Li-Jin Ke; Xiang-Xu Pan; Yu-Jui Ho; et al. (Science of The Total Environment, 2024)

Construction, characterization, antioxidant activity and effects on properties in vitro digestion of selenium nanoparticles decorated with Cyperus esculentus polysaccharides - Chuang Zhai; Yicun Lin; Chunling Mao; Xinxin Li; Ran Zhang; Jiaming Liu; Ling Zhang (Food Bioscience, 2024)

Sophisticated construction of single-atom cobalt catalyst based on microbial hyphae for high-performance hydrogenation - Junhua Kuang; Minghao Gong; Gaofeng Chen; Li Peng; Chen Zou; Zhiqing Peng; Weiming Chen; Yin Li; Yuting Zhang; Tianwei Xue; Chuang Li; Yangyang Dong; et al. (Chemical Engineering Journal, 2024)

Examining arterial pulsation to identify and risk-stratify heart failure subjects with deep neural network - Chieh-Chun Huang; Shih-Hsien Sung; Wei-Ting Wang; Yin-Yuan Su; Chi-Jung Huang; Tzu-Yu Chu; Shao-Yuan Chuang; Chern-En Chiang; Chen-Huan Chen; Chen-Ching Lin; Hao-Min Cheng (Physical and Engineering Sciences in Medicine, 2024)
Hemodynamic parameters derived from pulse wave analysis have been shown to predict long-term outcomes in patients with heart failure (HF). Here we aimed to develop a deep-learning based algorithm that incorporates pressure waveforms for the identification and risk stratification of patients with HF. The first study, with a case–control study design to address data imbalance issue, included 431 subjects with HF exhibiting typical symptoms and 1545 control participants with no history of HF (non-HF). Carotid pressure waveforms were obtained from all the participants using applanation tonometry. The HF score, representing the probability of HF, was derived from a one-dimensional deep neural network (DNN) model trained with characteristics of the normalized carotid pressure waveform. In the second study of HF patients, we constructed a Cox regression model with 83 candidate clinical variables along with the HF score to predict the risk of all-cause mortality along with rehospitalization. To identify subjects using the HF score, the sensitivity, specificity, accuracy, F1 score, and area under receiver operating characteristic curve were 0.867, 0.851, 0.874, 0.878, and 0.93, respectively, from the hold-out cross-validation of the DNN, which was better than other machine learning models, including logistic regression, support vector machine, and random forest. With a median follow-up of 5.8 years, the multivariable Cox model using the HF score and other clinical variables outperformed the other HF risk prediction models with concordance index of 0.71, in which only the HF score and five clinical variables were independent significant predictors (p < 0.05), including age, history of percutaneous coronary intervention, concentration of sodium in the emergency room, N -terminal pro-brain natriuretic peptide, and hemoglobin. Our study demonstrated the diagnostic and prognostic utility of arterial waveforms in subjects with HF using a DNN model. Pulse wave contains valuable information that can benefit the clinical care of patients with HF.

Particulate matter deposition and its impact on tuberculosis severity: A cross-sectional study in Taipei - Firdian Makrufardi; Hsiao-Chi Chuang; Chi-Won Suk; Yuan-Chien Lin; Desy Rusmawatiningtyas; Indah Kartika Murni; Eggi Arguni; Kian Fan Chung; Kuan-Jen Bai (Science of The Total Environment, 2024)

Novel magnetic separable BiOBr@Fe3O4 p-n heterostructure with highly efficient photocatalytic property toward organic pollutants - Kebena Gebeyehu Motora; Chang-Mou Wu; Meng-Chi Chuang; Szu-Tsen Lin (Journal of Water Process Engineering, 2024)

Decoding the genome of bloodsucking midge Forcipomyia taiwana (Diptera: Ceratopogonidae): Insights into odorant receptor expansion - Ming-Der Lin; Chia-Hsien Chuang; Chih-Hsin Kao; Shu-Hwa Chen; Szu-Chieh Wang; Ping-Heng Hsieh; Guan-Yu Chen; Chun-Chia Mao; Jeng-Yi Li; Mei-Yeh Jade Lu; Chung-Yen Lin (Insect Biochemistry and Molecular Biology, 2024)

Characteristics and impacts of fine particulates from the largest power plant plume in Taiwan - Ming-Tung Chuang; Charles C.-K Chou; Chung-Te Lee; Ja-Huai Lee; Wei-Che Lin; Chuan-Yao Lin; Wei-Nai Chen; Yi-Ying Chen; Kai-Hsien Chi (Atmospheric Pollution Research, 2024)

Zinc application facilitates the turnover of organic phosphorus in rice rhizosphere soil by modifying microbial communities - Haihan Lv; Jingli Ding; Lin Zhang; Chuang Wang; Hongmei Cai (Plant and Soil, 2024)

The polyphenols profile of co-fermented quinoa and black barley with Lactobacillus kisonensis and its in vitro bioactivities - Hui-Bin Jiang; Pan Nie; Zi-Han Lin; Chuang Zhu; Ling-Yue Zhong; Fen-Fen Wei; Yan Wu; Li-Hua Song (Food Bioscience, 2024)

Force-activated ratiometric fluorescence switching of tensile mechano-fluorophoric polyurethane elastomers with enhanced toughnesses improved by mechanically interlocked [c2] daisy chain rotaxanes - Tu Thi Kim Cuc; Chen-Hao Hung; Ting-Chi Wu; Pham Quoc Nhien; Trang Manh Khang; Bui Thi Buu Hue; Wei-Tsung Chuang; Hong-Cheu Lin (Chemical Engineering Journal, 2024)

Impact of occupational noise exposure on the hearing level in hospital staffs: a longitudinal study - Tang-Chuan Wang; You-Cheng Yu; Alan Hsu; Jia-Yi Lin; Yung-An Tsou; Chiu-Shong Liu; Kai-Jen Chuang; Wen-Chi Pan; Chin-An Yang; Sung-Lin Hu; Chien-Yi Ho; Tzu-Liang Chen; et al. (Environmental Science and Pollution Research, 2024)

Application of proteomics in identifying crucial virulence factors shared by different Streptococcus iniae isolates for developing an effective subunit vaccine against S. iniae in tilapia - Chaio-Ping Chen; Shu-Chun Chuang; Kuan-Lun Su; Li-Kai Chen; Yi-Chen Lin; Yu-Jen Wu; Shang-Pin Liu; Shao-Wen Hung; Chung-Hwan Chen; Chung-Da Yang (Aquaculture, 2024)

Emergence of OXA-48-producing hypervirulent Klebsiella pneumoniae strains in Taiwan - Yi-Tsung Lin; Chien Chuang; Sheng-Hua Chou; Chih-Han Juan; Tsuey-Ching Yang; Barry N. Kreiswirth; Liang Chen (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Aridity drives the variability of desert soil microbiomes across north-western China - Lei Dong; Mei-Xiang Li; Shuai Li; Ling-Xiang Yue; Mukhtiar Ali; Jia-Rui Han; Wen-Hui Lian; Chao-Jian Hu; Zhi-Liang Lin; Guo-Yuan Shi; Pan-Deng Wang; Shao-Ming Gao; et al. (Science of The Total Environment, 2024)

Application of nZnO supported with nanoclay for improving shrimp immunity - Zhen-Hao Liao; Chieh-Yuan Chuang; Yin-Yu Chen; Yu-Ting Chu; Yeh-Fang Hu; Po-Tsang Lee; Jiang-Jen Lin; Fan-Hua Nan (Fish & Shellfish Immunology, 2024)

Genetic diversity and relatedness of feline parvovirus in Vietnam and its potential implications for canine-feline transmission - Hoang Minh; Nguyen Vu Son; Hoang Minh Duc; Chao-Nan Lin; Yu-Chung Tyan; Kuo-Pin Chuang (Archives of Virology, 2024)

The joint association of ambient air pollution and different sleep posture with mild obstructive sleep apnea: A study conducted at Taipei Sleep Center - Yansu He; Wen-Te Liu; Shangyang Lin; Zhiyuan Li; Hong Qiu; Steve Hung Lam Yim; Hsiao-Chi Chuang; Kin Fai Ho (Science of The Total Environment, 2023)

Short-term mediating effects of PM2.5 on climate-associated COPD severity - Huan Minh Tran; Yuan-Chien Lin; Feng-Jen Tsai; Kang-Yun Lee; Jer-Hwa Chang; Chi-Li Chung; Kian Fan Chung; Kai-Jen Chuang; Hsiao-Chi Chuang (Science of The Total Environment, 2023)

Proposal, process development, and multi-aspect investigation of a novel environmentally friendly multigeneration process in arrangement with a sea water desalination unit - Fuxing Lin; Jianhua Wang; Tirumala Uday Kumar Nutakki; Mohamed Ayadi; Sayed Fayaz Ahmad; Taseer Muhammad; Chuang Lui (Journal of Environmental Chemical Engineering, 2023)

Species-specific primers in multiplex PCR for Bactrocera minax identification using an internal transcribed spacer - Prakriti Regmi; Cheng-Lung Tsai; Ming-Ying Lin; Yi-Yuan Chuang; Wen-Bin Yeh (Journal of Asia-Pacific Entomology, 2023)

Greenwater due to plunging breaking wave impingement on a deck structure. Part 1: Experimental investigation on fluid kinematics - Wei-Liang Chuang; Ting-Chieh Lin; Yu-Jan Wang (Ocean Engineering, 2023)

Exposure to bisphenol A associated with multiple health-related outcomes in humans: An umbrella review of systematic reviews with meta-analyses - Mao-Hsun Lin; Chun-Ying Lee; Yun-Shiuan Chuang; Chia-Lung Shih (Environmental Research, 2023)

Prenatal and postnatal exposure to heavy metals in PM2.5 and autism spectrum disorder - Hao-Hsuan Lin; Chau-Ren Jung; Chuan-Yao Lin; Ya-Chu Chang; Chia-Yun Hsieh; Pei-Chuan Hsu; Bao-Ru Chuang; Bing-Fang Hwang (Environmental Research, 2023)

Undercovering the role of physicochemical properties of amides in two-phase absorbent systems for ship exhaust pollutant removals - Junxiong Zhao; Yan Yang; Chuang Lei; Shengchao Xu; Hao Lin; Qifeng Wei; Xiulian Ren (Chemical Engineering Journal, 2023)

Performance analyses of two-phase closed thermosyphons for road embankments in the high-latitude permafrost regions - Guan-fu Wang; Chuang Lin; Long Zhu; De-cheng Feng; Yang-yang Xin; Feng Zhang (Journal of Mountain Science, 2023)

Decreased levels of perfluoroalkyl substances in patients receiving hemodialysis treatment - Jih-Kai Huang; Yun-Shiuan Chuang; Ping-Hsun Wu; Chi-Jung Tai; Jye-Ru Lin; Mei-Chuan Kuo; Yi-Wen Chiu; Ping-Chi Hsu; Ming-Tsang Wu; Samira Salihovic; Yi-Ting Lin (Science of The Total Environment, 2023)

Using drone soundings to study the impacts and compositions of plumes from a gigantic coal-fired power plant - Yen-Chen Chen; Jia-Lin Wang; Chih-Yuan Chang; Ming-Tung Chuang; Charles C.-K. Chou; Xiang-Xu Pan; Yu-Jui Ho; Chang-Feng Ou-Yang; Wen-Tzu Liu; Chih-Chung Chang (Science of The Total Environment, 2023)

Roles of waste carbon fibers on the efficiency of multiple induction heating healing behavior in asphalt mixture for sustainable infrastructure - Xiangqian Ye; Zhenyong Xiao; Chuang He; Wenyu Li; Peng Lin; Yuanyuan Meng; Chichun Hu (Journal of Cleaner Production, 2023)

Reexamination of traditional testing techniques for determining WRCs of woven geotextiles in full suction range - Chuang Lin; Yipeng Guo; Xiong Zhang; Javad Galinmoghadam (Geotextiles and Geomembranes, 2023)

Effects of ammonia on combustion of coal in stoichiometric premixed methane–air flames - Yueh-Heng Li; Bo-Cheng Chuang; Po-Hung Lin; Janusz Lasek (Fuel, 2023)

Novel visible-light-active P-g-CN-based α-Bi2O3/WO3 ternary photocatalysts with a dual Z-scheme heterostructure for the efficient decomposition of refractory ultraviolet filters and environmental hormones: Benzophenones - Abiyu Kerebo Berekute; Kuo-Pin Yu; Yi-Hsueh Brad Chuang; Kun-Yi Andrew Lin (Environmental Research, 2023)

The biocompatibility and hemostatic efficacy of silk fibroin nanofibrils fabricated by Shear-Induced phase separation process - Po-Wen Lu; Yu-Tzu Wu; Liang-Yu Chang; Tzu-Wei Lu; Chonlachat Jaihao; Ching-Shuan Huang; Mo-Fei Murphy Chuang; Chunche Lin; Innie Chen; Agnese Brangule; Aleksej Zarkov; Aivaras Kareiva; et al. (Chemical Engineering Journal, 2023)

Temporal transition trends of cord blood lead levels in various human development index countries and in the Taipei metropolitan area - Yaw-Huei Hwang; Hui-Chu Wu; Ming-Kwang Shyu; Chien-Nan Lee; Shin-Yu Lin; Pau-Chung Chen; Hung-Yi Chuang; Pei-Wen Lin; Tso-Hsien Wu; Yen-Tzu Chen (Environmental Pollution, 2023)

High carriage rate of extended‐spectrum β‐lactamase Enterobacterales and diarrheagenic Escherichia coli in healthy donor screening for fecal microbiota transplantation - Chien Chuang; Kuei-Chuan Lee; Yen-Po Wang; Pei-Chang Lee; Tien-En Chang; Yi-Hsiang Huang; Yi-Tsung Lin; Ming-Chih Hou (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Marine Collision Avoidance Route Planning Model for MASS Based on Domain-Based Predicted Area of Danger - Chao-Wei Lu; Chao-Kuang Hsueh; Yung-Lin Chuang; Ching-Ming Lai; Fuh-Shyong Yang (Journal of Marine Science and Engineering, 2023)
When the own ship encounters target ships in a close-quarter situation, an officer on watch needs to safely and timely alter the course of the vessel to avoid a collision. If ECDIS can automatically collect the navigation parameters and plot areas of collision as quasi-static obstruction areas, it will be much easier for seafarers to implement effective route planning. Hence, this study focuses on developing the MCARP model as a theoretical concept based on the DPAD model and LCD model. By operating the MCARP using ArcGIS, DPADs and several effective collision avoidance routes can be generated and imported into ECDIS based on AIS information at large scales and ample time. The graphic overlay of DPADs and effective routes on ECDIS can serve as a collision avoidance strategy reference for the personnel controlling maritime autonomous surface ships. Finally, different ships encountering situations were input into a Transas navigational simulator. The simulation results showed that own ship could avoid collisions with multiple target ships at distances larger than the preset collision avoidance distances, which also indicated that MCARP is practically feasible.

The association of bisphenol A and paraben exposure with sensorineural hearing loss in children - Chia-Huang Chang; Chun-Ting Lu; Tai-Ling Chen; Wen-Tzu Huang; Pao-Chuan Torng; Chen-Wei Chang; Yu-Chun Chen; Yu-Lin Yu; Yung-Ning Chuang (Environmental Science and Pollution Research, 2023)

Tiliroside induces ferroptosis to repress the development of triple-negative breast cancer cells - Chuang Hu; Jian-Fu Zhao; Yi-Ming Wang; Xian-lin Wu; Ling Ye (Tissue and Cell, 2023)

Air pollution exacerbates mild obstructive sleep apnea by disrupting nocturnal changes in lower-limb body composition: a cross-sectional study conducted in urban northern Taiwan - Yansu He; Wen-Te Liu; Shang-Yang Lin; Zhiyuan Li; Hong Qiu; Steve Hung-Lam Yim; Hsiao-Chi Chuang; Kin Fai Ho (Science of The Total Environment, 2023)

Integrated ground and vertical measurement techniques to characterize overhead atmosphere: Case studies of local versus transboundary pollution - Chang-Feng Ou-Yang; Chih-Chung Chang; Sheng-Hsiang Wang; Charles C.-K. Chou; Ming-Tung Chuang; Tang-Huang Lin; Wei-Nai Chen; Ta-Chih Hsiao; Ming-Cheng Yen; Yueh-Chen Wang; Neng-Huei Lin; Jia-Lin Wang (Science of The Total Environment, 2023)

Mechanisms of lead uptake and accumulation in wheat grains based on atmospheric deposition-soil sources - Chuang Ma; Lin Lin; Junxing Yang; Fuyong Liu; Mario Berrettoni; Ke Zhang; Nan Liu; Hongzhong Zhang (Science of The Total Environment, 2023)

New ent -kaurene and germacrene derivatives from Mesona procumbens Hemseley and their biological activity - Jerome G. Ganzon; Chia-Ching Liaw; Yu-Chi Lin; Zhi-Hu Lin; Chang-Hung Wang; Che-Yi Chen; Kuo-Hsiang Chuang; Yao-Haur Kuo (Natural Product Research, 2023)

Investigation of mechanical properties and elastoplastic numerical calculation model of frozen soil containing ice lenses - Sheng Shi; Feng Zhang; Decheng Feng; Chuang Lin (Cold Regions Science and Technology, 2023)

Retraction Note to: SOC1 and AGL24 interact with AGL18-1, not the other family members AGL18-2 and AGL18-3 in Brassica juncea - Chao-chuang Li; Guan-peng Ma; Ting Xie; Jiao Chen; Zhi-min Wang; Ming Song; Qing-lin Tang (Acta Physiologiae Plantarum, 2023)

Probing air pollution in the Taichung metropolitan area, Taiwan.Part 1: Comprehensive model evaluation and the spatial-temporal evolution of a PM2.5 pollution event - Ming-Tung Chuang; Charles C.-K. Chou; Chuan-Yao Lin; Ja-Huai Lee; Wei-Che Lin; Wei-Nai Chen; Chian-Yi Liu; Chih-Chung Chang (Atmospheric Research, 2023)

Evolution of reactive species and their contribution to the removal of ketamine and amine-containing pharmaceuticals during the sunlight/chlorine process - Yu-Hsiang Wang; Yi-Hsueh Chuang; Angela Yu-Chen Lin (Water Research, 2023)

Simplified nonlinear modeling for estimating the seismic response of buildings - Jui-Liang Lin; Ming-Chieh Chuang (Engineering Structures, 2023)

Ambient relative humidity-dependent obstructive sleep apnea severity in cold season: A case-control study - Kuan-Jen Bai; Wen-Te Liu; Yuan-Chien Lin; Yansu He; Yueh-Lun Lee; Dean Wu; Ta-Yuan Chang; Li-Te Chang; Chun-Yeh Lai; Cheng-Yu Tsai; Kian Fan Chung; Kin-Fai Ho; et al. (Science of The Total Environment, 2023)

Spatial allocation of LID practices with a water footprint approach - Wen-Kai Chuang; Zih-Ee Lin; Tzu-Chi Lin; Shang-Lien Lo; Chia-Lin Chang; Pei-Te Chiueh (Science of The Total Environment, 2023)

Comparison of controlled drugs and new psychoactive substances (NPS) regulations in East and Southeast Asia - Olivia A. Lin; Pei-Jiun Chuang; Y. Jane Tseng (Regulatory Toxicology and Pharmacology, 2023)

Experimental study on the shear characteristics of different pile-soil interfaces and the influencing factors - Chuang Lin; Guanfu Wang; Cong Guan; Decheng Feng; Feng Zhang (Cold Regions Science and Technology, 2023)

Analysis of microplastics released from plastic take-out food containers based on thermal properties and morphology study - Jia-Ling Hu; Yipin Duan; Huai-Ning Zhong; Qin-Bao Lin; Tianlong Zhang; Chuang-Chuang Zhao; Sheng Chen; Ben Dong; Dan Li; Jing Wang; Ming-Zhen Mo; Jie Chen; et al. (Food Additives & Contaminants: Part A, 2023)

Antiherbivore effect of Cuscuta campestris against Spodoptera frugiperda - Chang-Lin Sung; Fang-Yu Hu; Yi Li; Shin-Fu Tsai; Wen-Po Chuang (Arthropod-Plant Interactions, 2023)

Evaluating the release and metabolism of ricinine from castor cake fertilizer in soils using a LC-QTOF/MS coupled with SIRIUS workflow - Kai-Xuan Zheng; Cheng-Hua Liu; Sichao Wang; Yu-Min Tzou; Chih-Min Chiang; Shiou-Ruei Lin; Hsiao-Ying Yang; Jerry J. Wu; Ya-Hui Chuang (Chemosphere, 2023)

Quantifying food loss along the animal products supply chain in China with large-scale field-survey based primary data - Ruigang Wang; Gang Liu; Lin Zhou; Zhenni Yang; Zhenchuang Tang; Shijun Lu; Mingjun Zhao; Huiwu Sun; Chuang Ma; Guangyan Cheng (Resources, Conservation and Recycling, 2023)

Lamellar-structured anodes based on lithiophilic gradient enable dendrite-free lithium metal batteries with high capacity loading and fast-charging capability - Yucheng Liu; Chuang Sun; Yuhao Lu; Xiaoping Lin; Maohua Chen; Yuansen Xie; Chao Lai; Wen Yan (Chemical Engineering Journal, 2023)

Associations between gastrointestinal infection and urinary phthalate metabolite concentrations in US children and adolescents from NHANES 2005–2016 - Chuang Zhang; Weirui Ren; Chi Sun; Lin Liu; Meng Li; Wenbo Wang; Yanbin Fang; Lin Liu; Xiaofeng Yang; Xiangjian Zhang; Suolin Li (Environmental Science and Pollution Research, 2023)

Mesenchymal Stem Cell Secreted-Extracellular Vesicles are Involved in Chondrocyte Production and Reduce Adipogenesis during Stem Cell Differentiation - Yu-Chen Tsai; Tai-Shan Cheng; Hsiu-Jung Liao; Ming-Hsi Chuang; Hui-Ting Chen; Chun-Hung Chen; Kai-Ling Zhang; Chih-Hung Chang; Po-Cheng Lin; Chi-Ying F. Huang (Tissue Engineering and Regenerative Medicine, 2022)
Background: Extracellular vesicles (EVs) are derived from internal cellular compartments, and have potential as a diagnostic and therapeutic tool in degenerative disease associated with aging. Mesenchymal stem cells (MSCs) have become a promising tool for functional EVs production. This study investigated the efficacy of EVs and its effect on differentiation capacity. Methods: The characteristics of MSCs were evaluated by flow cytometry and stem cell differentiation analysis, and a production mode of functional EVs was scaled from MSCs. The concentration and size of EVs were quantitated by Nanoparticle Tracking Analysis (NTA). Western blot analysis was used to assess the protein expression of exosome-specific markers. The effects of MSC-derived EVs were assessed by chondrogenic and adipogenic differentiation analyses and histological observation. Results: The range of the particle size of adipose-derived stem cells (ADSCs)- and Wharton’s jelly -MSCs-derived EVs were from 130 to 150 nm as measured by NTA, which showed positive expression of exosomal markers. The chondrogenic induction ability was weakened in the absence of EVs in vitro . Interestingly, after EV administration, type II collagen, a major component in the cartilage extracellular matrix, was upregulated compared to the EV-free condition. Moreover, EVs decreased the lipid accumulation rate during adipogenic induction. Conclusion: The results indicated that the production model could facilitate production of effective EVs and further demonstrated the role of MSC-derived EVs in cell differentiation. MSC-derived EVs could be successfully used in cell-free therapy to guide chondrogenic differentiation of ADSC for future clinical applications in cartilage regeneration.

Breast cancer incidence in a national cohort of female workers exposed to special health hazards in Taiwan: a retrospective case-cohort study of ~ 300,000 occupational records spanning 20 years - Yun-Shiuan Chuang; Chun-Ying Lee; Pei-Chen Lin; Chih-Hong Pan; Hui-Min Hsieh; Chia-Fang Wu; Ming-Tsang Wu (International Archives of Occupational and Environmental Health, 2022)

Experimental Study on Pyrolysis of Rice Straw Catalyzed by CaO/Al2O3-Phosphate Mixture - Lianlian Xu; Zhongwen Xu; Feng Zhang; Yinmei Yuan; Bin Cheng; Chuang Zhang; Ping Chen; Xiangyong Huang; Yuyu Lin; Mingyan Gu (BioEnergy Research, 2022)

Theranostic Radiolabeled Nanomaterials for Molecular Imaging and potential Immunomodulation Effects - Chao-Cheng Chen; Yang-Hsiang Chan; Syue-Liang Lin; Huihua Kenny Chiang; Yi-Jang Lee; Hui-Yen Chuang (Journal of Medical and Biological Engineering, 2022)

Sex differences in microstructural alterations in the corpus callosum tracts in drug-naïve children with ADHD - Qingxia Lin; Xuan Bu; Hong Chen; Yan Liang; Weiqian Wang; Yanhong Yi; Haixi Lin; Lu Lu; Yingxue Gao; Andan Qian; Shuangli Chen; Meihao Wang; et al. (Brain Imaging and Behavior, 2022)

Estrogenic and anti-neutrophilic inflammatory phenanthrenes from Juncus effusus L. - Hao-Chun Hu; Yi-Hong Tsai; Yu-Che Chuang; Kuei-Hung Lai; Yu-Ming Hsu; Tsong-Long Hwang; Chih-Chan Lin; Ferenc Fülöp; Yang-Chang Wu; Szu-Yin Yu; Yu-Ting Kuo; Fang-Rong Chang (Natural Product Research, 2022)

Use of piggyBac Transposon System Constructed Murine Breast Cancer Model for Reporter Gene Imaging and Characterization of Metastatic Tumor Cells - Ying-Ling Chen; Yung-Cheng Wang; Kuei-Yuan Hou; Min-Ying Lin; Yu-Chuan Lin; Hui-Yen Chuang; Yi-Jang Lee (Journal of Medical and Biological Engineering, 2022)

Natural Feed Supplements Improve Growth, Non-Specific Immune Responses and Resistance against Vibrio alginolyticus in Lates calcarifer - Zhen-Hao Liao; Huai-Ting Huang; Yu-Ru Lin; Bo-Ying Chen; Yi-Fan Lee; Yuan-Heng Lin; Chieh-Yuan Chuang; Fan-Hua Nan (Journal of Marine Science and Engineering, 2022)
This study aimed to investigate the effects of dietary natural feed supplement on the growth performance, non-specific responses, and disease resistance in Lates calcarifer. Three commercial products (A, B, and C) containing a basal probiotic mixture were tested. Product A contained a basal mixture of Paenibacillus sp., Bacillus subtilis, Bacillus amyloliquefaciens, and Lactobacillus rhamnosus (107 cfu/g for each probiotic); product B contained additional Lactobacillus plantarum (1010 cfu/g); and product C contained additional soybean peptides (500 g/kg) and garlic powder (1 g/kg). Each product was supplemented into subject diets at dosages of 1 or 2 g/kg (designated as the A1, A2, B1, B2, C1, and C2 groups, respectively). Following an eight-week trial, growth parameters (specific growth rate and feed conversion ratio), non-specific immune responses (O2− production, phagocytic rate, and phagocytic index), and the results of a challenge test against Vibrio alginolyticus were evaluated. The results show that all probiotic supplement groups exhibited an improvement in growth performance compared to the control group (non-probiotic diet). In terms of non-specific immunity parameters, a significant improvement in O2− production was found in the C2 group, whereas significant improvements in phagocytic activity were found in all the B and C groups. The C2 group displayed optimal O2− production, phagocytic rate, and phagocytic index results. For the challenge test, the C groups showed higher Vibrio resistance than the other experimental groups and the control group. These results suggest that product C, given at dosages of 2 g/kg, may serve as a growth-promoting and immunostimulatory additive for the cultivation of Asian seabass.

Different effects of the DRD4 genotype on intrinsic brain network connectivity strength in drug-naïve children with ADHD and healthy controls - Shuangli Chen; Andan Qian; Jiejie Tao; Ronghui Zhou; Chuqi Fu; Chuang Yang; Qingxia Lin; JieJie Zhou; Jiance Li; Xiaoqi Huang; Meihao Wang (Brain Imaging and Behavior, 2022)
The dopamine D4 receptor gene (DRD4) has been consistently reported to be associated with attention-deficit/hyperactivity disorder (ADHD). Recent studies have linked DRD4 to functional connectivity among specific brain regions. The current study aimed to compare the effects of the DRD4 genotype on functional integrity in drug-naïve ADHD children and healthy children. Resting-state functional MRI images were acquired from 49 children with ADHD and 37 healthy controls (HCs). We investigated the effects of the 2-repeat allele of DRD4 on brain network connectivity in both groups using a parameter called the degree of centrality (DC), which indexes local functional relationships across the entire brain connectome. A voxel-wise two-way ANCOVA was performed to examine the diagnosis-by-genotype interactions on DC maps. Significant diagnosis-by-genotype interactions with DC were found in the temporal lobe, including the left inferior temporal gyrus (ITG) and bilateral middle temporal gyrus (MTG) (GRF corrected at voxel level p < 0.001 and cluster level p < 0.05, two-tailed). With the further subdivision of the DC network according to anatomical distance, additional brain regions with significant interactions were found in the long-range DC network, including the left superior parietal gyrus (SPG) and right middle frontal gyrus (MFG). The post-hoc pairwise analysis found that altered network centrality related to DRD4 differed according to diagnostic status (p < 0.05). This genetic imaging study suggests that the DRD4 genotype regulates the functional integration of brain networks in children with ADHD and HCs differently. This may have important implications for our understanding of the role of DRD4 in altering functional connectivity in ADHD subjects.

Sabulicella rubraurantiaca gen. nov., sp. nov., a new member of the family Acetobacteraceae, isolated from desert soil - Zhi-Liang Lin; Shuai Li; Qi-Chuang Wei; Wen-Hui Lian; Chun-Yan Lu; Lu Xu; Li-Nan Huang; Lei Dong; Wen-Jun Li (Archives of Microbiology, 2022)

Intramyocardial injection of human adipose-derived stem cells ameliorates cognitive deficit by regulating oxidative stress–mediated hippocampal damage after myocardial infarction - Tsung-Ming LEE; Cheng-Che LEE; Horng-Jyh HARN; Tzyy-Wen Chiou; Ming-Hsi CHUANG; Chun-Hung CHEN; Chi-Hsuan CHUANG; Po-Cheng LIN; Shinn-Zong LIN (Journal of Molecular Medicine, 2021)
Cognitive impairment is a serious side effect of post-myocardial infarction (MI) course. We have recently demonstrated that human adipose-derived stem cells (hADSCs) ameliorated myocardial injury after MI by attenuating reactive oxygen species (ROS) levels. Here, we studied whether the beneficial effects of intramyocardial hADSC transplantation can extend to the brain and how they may attenuate cognitive dysfunction via modulating ROS after MI. After coronary ligation, male Wistar rats were randomized via an intramyocardial route to receive either vehicle, hADSC transplantation (1 × 10 6 cells), or the combination of hADSCs and 3-Morpholinosydnonimine (SIN-1, a peroxynitrite donor). Whether hADSCs migrated into the hippocampus was assessed by using human-specific primers in qPCR reactions. Passive avoidance test was used to assess cognitive performance. Postinfarction was associated with increased oxidative stress in the myocardium, circulation, and hippocampus. This was coupled with decreased numbers of dendritic spines as well as a significant downregulation of synaptic plasticity consisting of synaptophysin and PSD95. Step-through latency during passive avoidance test was impaired in vehicle-treated rats after MI. Intramyocardial hADSC injection exerted therapeutic benefits in improving cardiac function and cognitive impairment. None of hADSCs was detected in rat’s hippocampus at the 3rd day after intramyocardial injection. The beneficial effects of hADSCs on MI-induced histological and cognitive changes were abolished after adding SIN-1. MI-induced ROS attacked the hippocampus to induce neurodegeneration, resulting in cognitive deficit. The remotely intramyocardial administration of hADSCs has the capacity of improved synaptic neuroplasticity in the hippocampus mediated by ROS, not the cell engraftment, after MI. Key messages Human adipose-derived stem cells (hADSCs) ameliorated injury after myocardial infarction by attenuating reactive oxygen species (ROS) levels. Intramyocardial administration of hADSCs remotely exerted therapeutic benefits in improving cognitive impairment after myocardial infarction. The improved synaptic neuroplasticity in the hippocampus was mediated by hADSC-inhibiting ROS, not by the stem cell engraftment.

Effect of heat stress on oxidative damage and antioxidant defense system in white clover (Trifolium repens L.) - Hsiang-Lin Liu; Zhu-Xuan Lee; Tzu-Wei Chuang; Hui-Chen Wu (Planta, 2021)

Understanding the East Asian winter monsoon in 2018 from the intraseasonal perspective - Lin Wang; Chuang Zheng; Yuyun Liu (Climate Dynamics, 2021)

Cortisol and glucocorticoid receptor 2 regulate acid secretion in medaka (Oryzias latipes) larvae - Chia-Hao Lin; Huei-Jyun Hu; Hsin-Ju Chuang; Yi-Ling Tsou; Pung-Pung Hwang (Journal of Comparative Physiology B, 2021)

Risk of two common glandular cell-type cancers (breast and colorectal cancers) in Chinese occupational chefs: a nationwide ecological study in Taiwan - Pei-Chen Lin; Chiung‑Yu Peng; Chih‑Hong Pan; Jui-Ying Lee; Tusty-Jiuan Hsieh; Yun-Shiuan Chuang; Robert J. Turesky; Chia-Fang Wu; Ming-Tsang Wu (International Archives of Occupational and Environmental Health, 2021)

Actirhodobacter atriluteus gen. nov., sp. nov., isolated from the surface water of the Yellow Sea - Hua-Peng Xue; Dao-Feng Zhang; Lin Xu; Xiang-Ning Wang; Ai-Hua Zhang; Jian-Ke Huang; Chuang Liu (Antonie van Leeuwenhoek, 2021)

Evidence-based Customized Ankle-Foot Orthosis with Energy Storage - Chih-Chun Lin; Chien-Hsien Yeh; Yi-Chun Tsai; Li-Chieh Kuo; Hsiu-Yun Hsu; Ping-Han Chuang; Kai Chang; Fong-Chin Su (Journal of Medical and Biological Engineering, 2021)

Natural polyketide 6-pentyl-2 H -pyrone-2-one and its synthetic analogues efficiently prevent marine biofouling - Mo Aqib Raza Khan; Bo-Wei Wang; Yih-Yu Chen; Ting-Hsuan Lin; Hsiu-Chin Lin; Yu-Liang Yang; Ka-Lai Pang; Chih-Chuang Liaw (Biofouling, 2021)

Street-block collapsed buildings assessment: A case study of Banqiao District, New Taipei City - ITien Lo; ChingYuan Lin; ChengTao Yang; YingJi Chuang; ChiHao Lin (Earth Science Informatics, 2021)

Changes in arthropod community but not plant quality benefit a specialist herbivore on plants under reduced water availability - Po-An Lin; Chia-Ming Liu; Jia-Ang Ou; Cheng-Han Sun; Wen-Po Chuang; Chuan-Kai Ho; Natsuko Kinoshita; Gary W. Felton (Oecologia, 2021)

Gentianella acuta prevents acute myocardial infarction induced by isoproterenol in rats via inhibition of galectin-3/TLR4/MyD88/NF-кB inflammatory signalling - Jia-Huan Sun; Hong-Xia Yang; Ting-Ting Yao; Yuan Li; Lin Ruan; Geng-Rui Xu; Chuang Zhang; Guo-Xin Guo; Ai-Ying Li (Inflammopharmacology, 2021)

A drug-tunable Flt23k gene therapy for controlled intervention in retinal neovascularization - Jinying Chen; Fan-Li Lin; Jacqueline Y. K. Leung; Leilei Tu; Jiang-Hui Wang; Yu-Fan Chuang; Fan Li; Hsin-Hui Shen; Gregory J. Dusting; Vickie H. Y. Wong; Leszek Lisowski; Alex W. Hewitt; et al. (Angiogenesis, 2021)

Correction to: 4-Phenylbutyric acid protects against vasculitic peripheral neuropathy induced by ischaemia–reperfusion through attenuating endoplasmic reticulum stress - Cay‑Huyen Chen; Ping‑Chen Shih; Han‑Yu Lin; Po‑Kai Wang; Po‑Ting Pan; Ching‑Wei Chuang; Ming‑Chang Kao (Inflammopharmacology, 2020)

Correction to: Effects of Collagen Crosslink Augmentation on Mechanism of Compressive Load Sharing in Intervertebral Discs - Thomas P. Hedman; Weng-Pin Chen; Leou-Chyr Lin; Hsiu-Jen Lin; Shih-Youeng Chuang (Journal of Medical and Biological Engineering, 2020)
After publication in volume [37], issue [1], page [94–101] the authors decided to opt for Open Choice and to make the article an open access publication. Therefore, the copyright of the article has been changed to © The Author(s) 2018 and the article is forthwith distributed under the terms of the Creative Commons Attribution 4.0 International License (http://creativecommons.org/licenses/by/4.0/), which permits use, duplication, adaptation, distribution and reproduction in any medium or format, as long as you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons license, and indicate if changes were made.

Upregulation of miR-133a-3p in the Sciatic Nerve Contributes to Neuropathic Pain Development - Lin-Li Chang; Hung-Chen Wang; Kuang-Yi Tseng; Miao-Pei Su; Jaw-Yuan Wang; Yi-Ta Chuang; Yi-Hsuan Wang; Kuang-I Cheng (Molecular Neurobiology, 2020)

Bias Adjustment of Satellite Precipitation Estimation Using Ground-Based Observation: Mei-Yu Front Case Studies in Taiwan - Nan-Ching Yeh; Yao-Chung Chuang; Hsin-Shuo Peng; Kuo-Lin Hsu (Asia-Pacific Journal of Atmospheric Sciences, 2020)
The Global Satellite Mapping of Precipitation (GSMaP) was used to estimate the accumulated rainfall in May from the Mei-Yu front in Taiwan. Rainfall estimation from GSMaP during 2002–2017 were evaluated using more than 400 local gauge observations, collected from the Taiwan Central Weather Bureau (CWB). Studies have demonstrated that the GSMaP rainfall estimation estimates can be biased, depending on the target region, elevation, and season. In this experiment, we have evaluated GSMaP over three elevation ranges. The GSMaP systemic errors for each elevation range were identified and corrected using regression analysis. The results indicated that GSMaP estimation can be improved significantly through adjustment over three elevation ranges (elevation less than 50 m, elevation of 50–100 m, and elevation higher than 100 m). For these three elevation ranges, the correlation coefficient between the GSMaP estimations and CWB rainfall data was 0.76, 0.78, and 0.59, respectively. This indicated that the GSMaP estimation was more accurate for low-elevation regions than high-elevation regions. After the proposed approaches were employed to correct the errors, the bias errors were respectively improved by 5.64(13.7%), 7.33(38.4%) and 10.52(31.2%) mm for low-, mid- and high-elevation regions. This study demonstrated that the local correction approaches can be used to improve GSMaP estimation of Mei-Yu rainfall in Taiwan.

Aberrant white matter properties of the callosal tracts implicated in girls with attention-deficit/hyperactivity disorder - Qingxia Lin; Xuan Bu; Meihao Wang; Yan Liang; Hong Chen; Weiqian Wang; Yanhong Yi; Haixi Lin; Jiaxiu Zhou; Lu Lu; Xinyu Hu; Chuang Yang; et al. (Brain Imaging and Behavior, 2020)

Diverse Community Structures in the Neuronal-Level Connectome of the Drosophila Brain - Chi-Tin Shih; Yen-Jen Lin; Cheng-Te Wang; Ting-Yuan Wang; Chih-Chen Chen; Ta-Shun Su; Chung-Chuang Lo; Ann-Shyn Chiang (Neuroinformatics, 2020)

The acclimation of leaf photosynthesis of wheat and rice to seasonal temperature changes in T‐FACE environments - Chuang Cai; Gang Li; Lijun Di; Yunjie Ding; Lin Fu; Xuanhe Guo; Paul C. Struik; Genxing Pan; Haozheng Li; Weiping Chen; Weihong Luo; Xinyou Yin (Global Change Biology, 2020)
Crops show considerable capacity to adjust their photosynthetic characteristics to seasonal changes in temperature. However, how photosynthesis acclimates to changes in seasonal temperature under future climate conditions has not been revealed. We measured leaf photosynthesis ( A n ) of wheat ( Triticum aestivum L.) and rice ( Oryza sativa L.) grown under four combinations of two levels of CO 2 (ambient and enriched up to 500 µmol/mol) and two levels of canopy temperature (ambient and increased by 1.5–2.0°C) in temperature by free‐air CO 2 enrichment (T‐FACE) systems. Parameters of a biochemical C 3 ‐photosynthesis model and of a stomatal conductance ( g s ) model were estimated for the four conditions and for several crop stages. Some biochemical parameters related to electron transport and most g s parameters showed acclimation to seasonal growth temperature in both crops. The acclimation response did not differ much between wheat and rice, nor among the four treatments of the T‐FACE systems, when the difference in the seasonal growth temperature was accounted for. The relationships between biochemical parameters and leaf nitrogen content were consistent across leaf ranks, developmental stages, and treatment conditions. The acclimation had a strong impact on g s model parameters: when parameter values of a particular stage were used, the model failed to correctly estimate g s values of other stages. Further analysis using the coupled g s –biochemical photosynthesis model showed that ignoring the acclimation effect did not result in critical errors in estimating leaf photosynthesis under future climate, as long as parameter values were measured or derived from data obtained before flowering.

Comparative health risk of inhaled exposure to organic solvents, toxic metals, and hexavalent chromium from the use of spray paints in Taiwan - Chia-Hua Lin; Chia-Hsiang Lai; Yen-Ping Peng; Pei-Chun Wu; Kuen-Yuan Chuang; Ting-Yu Yen; Yao-Kai Xiang (Environmental Science and Pollution Research, 2019)

4-Phenylbutyric acid protects against vasculitic peripheral neuropathy induced by ischaemia–reperfusion through attenuating endoplasmic reticulum stress - Cay-Huyen Chen; Ping-Chen Shih; Han-Yu Lin; Po-Kai Wang; Po-Ting Pan; Ching-Wei Chuang; Ming-Chang Kao (Inflammopharmacology, 2019)

Dynamic monitoring of resuspension in the multiple eco-types of the littoral zone of a shallow wind-disturbed lake - Chuang Qi; Yang Zhou; Xiao-guang Xu; Li-min Zhang; Hui Lin; Xin-ting Wu; Kuan Shi; Guo-xiang Wang (Aquatic Sciences, 2019)

In situ resuspension rate monitoring method in the littoral zone with multi-ecotypes of a shallow wind-disturbed lake - Chuang Qi; Xiao-guang Xu; Kuan Shi; Li-min Zhang; Yang Zhou; Hui Lin; Xin-ting Wu; Guo-xiang Wang; Han Meng (Environmental Science and Pollution Research, 2019)

Far-infrared Radiation Improves Motor Dysfunction and Neuropathology in Spinocerebellar Ataxia Type 3 Mice - Shin-Wu Liu; Jui-Chih Chang; Sheng-Fei Chuang; Ko-Hung Liu; Wen-Ling Cheng; Hui-Ju Chang; Huei-Shin Chang; Ta-Tsung Lin; Ching-Liang Hsieh; Wei-Yong Lin; Mingli Hsieh; Shou-Jen Kuo; et al. (The Cerebellum, 2019)

The fecal virome of red-crowned cranes - Yan Wang; Shixing Yang; Dawei Liu; Chenglin Zhou; Wang Li; Yuan Lin; Xiaochun Wang; Quan Shen; Hua Wang; Chuang Li; Minghui Zong; Yuzhu Ding; et al. (Archives of Virology, 2019)

Pre-treatment with angiotensin-(1–7) inhibits tumor growth via autophagy by downregulating PI3K/Akt/mTOR signaling in human nasopharyngeal carcinoma xenografts - Yu-Tsai Lin; Hung-Chen Wang; Hui-Ching Chuang; Yi-Chiang Hsu; Ming-Yu Yang; Chih-Yen Chien (Journal of Molecular Medicine, 2018)

Tacrine(10)-hupyridone, a dual-binding acetylcholinesterase inhibitor, potently attenuates scopolamine-induced impairments of cognition in mice - Huixin Chen; Siying Xiang; Ling Huang; Jiajia Lin; Shengquan Hu; Shing-Hung Mak; Chuang Wang; Qinwen Wang; Wei Cui; Yifan Han (Metabolic Brain Disease, 2018)

Extension of C. elegans lifespan using the ·NO-delivery dinitrosyl iron complexes - Hsiao-Wen Huang; Yen-Hung Lin; Min-Hsuan Lin; Ya-Rong Huang; Chih-Hung Chou; Hsiao-Chin Hong; Mei-Ren Wang; Yu-Ting Tseng; Po-Chun Liao; Min-Chuan Chung; Yu-Jie Ma; Shou-Cheng Wu; et al. (JBIC Journal of Biological Inorganic Chemistry, 2018)

MDM2 Degrades Deacetylated Nucleolin Through Ubiquitination to Promote Glioma Stem-Like Cell Enrichment for Chemotherapeutic Resistance - Chiung-Yuan Ko; Chao-Han Lin; Jian-Ying Chuang; Wen-Chang Chang; Tsung-I Hsu (Molecular Neurobiology, 2018)

Improving the management of Taiwanese fishery resource conservation zones based on public perceptions and willingness to pay for ecosystem services - Jyun-Long Chen; Yu-Sheng Lin; Ching-Ta Chuang (Journal of Coastal Conservation, 2018)

Treatment outcome of non-carbapenemase-producing carbapenem-resistant Klebsiella pneumoniae infections: a multicenter study in Taiwan - Chin-Fang Su; Chien Chuang; Yi-Tsung Lin; Yu-Jiun Chan; Jung-Chung Lin; Po-Liang Lu; Ching-Tai Huang; Jann-Tay Wang; Yin-Ching Chuang; L. Kristopher Siu; Chang-Phone Fung (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Impacts of hydrogeological characteristics on groundwater-level changes induced by earthquakes - Ching-Yi Liu; Yeeping Chia; Po-Yu Chuang; Yung-Chia Chiu; Tai-Lin Tseng (Hydrogeology Journal, 2018)

Fast trace determination of nine odorant and estrogenic chloro- and bromo-phenolic compounds in real water samples through automated solid-phase extraction coupled with liquid chromatography tandem mass spectrometry - Su-fen Yuan; Ze-hua Liu; Hai-xian Lian; Chuang-tao Yang; Qing Lin; Hua Yin; Zhang Lin; Zhi Dang (Environmental Science and Pollution Research, 2018)

RETRACTED ARTICLE: SOC1 and AGL24 interact with AGL18-1, not the other family members AGL18-2 and AGL18-3 in Brassica juncea - Chao-chuang Li; Guan-peng Ma; Ting Xie; Jiao Chen; Zhi-min Wang; Ming Song; Qing-lin Tang (Acta Physiologiae Plantarum, 2018)

Community responses to dam removal in a subtropical mountainous stream - Hao-Yen Chang; Ming-Chih Chiu; Yi-Li Chuang; Chyng-Shyan Tzeng; Mei-Hwa Kuo; Chao-Hsien Yeh; Hsiao-Wen Wang; Sheng-Hai Wu; Wen-Hui Kuan; Shang-Te Tsai; Kwang-Tsao Shao; Hsing-Juh Lin (Aquatic Sciences, 2017)

The effects and the toxicity increases caused by bicarbonate, chloride, and other water components during the UV/TiO2 degradation of oxazaphosphorine drugs - Webber Wei-Po Lai; Ying-Chih Chuang; Angela Yu-Chen Lin (Environmental Science and Pollution Research, 2017)

Effects of Collagen Crosslink Augmentation on Mechanism of Compressive Load Sharing in Intervertebral Discs - Thomas P. Hedman; Weng-Pin Chen; Leou-Chyr Lin; Hsiu-Jen Lin; Shih-Youeng Chuang (Journal of Medical and Biological Engineering, 2017)
Exogenous crosslinking has been shown to have potential for treating disc degeneration and back pain due to its ability to increase the strength and toughness of the annulus fibrosus, increase intervertebral joint stability, decrease intradiscal pressure, and increase fluid flow through the disc. Some results imply that crosslink augmentation may also lead to changes in the compressive load sharing properties of the disc. The objective of the present study was to evaluate directional stress distribution changes of the disc following genipin crosslinking treatment. Bovine lumbar motion segments were randomly divided into control and crosslinked groups. Annular strains were determined from simultaneous deformation measurements at various time points during compressive creep testing. Four stress components of the annulus were then calculated according to the previously measured modulus data. Immediately after the application of a 750-N compressive load, mean axial and radial compressive stresses in the crosslinked group were twofold higher than control means. Conversely, mean lamellae-aligned and circumferential tensile stresses of the crosslinked discs were 8- and threefold lower, respectively, compared to control means. After 1-h creep loading, the two compressive mean stresses in both the control and genipin-crosslinked specimens increased approximately threefold from their initial 750-N-loaded values. The two tensile mean stresses in the crosslinked group remained lower than the respective levels of the control means after creep loading. A greater proportion of annular compressive load support under compressive creep loading, with a commensurate decrease in both tensile stresses and strains, was seen in the discs following exogenous crosslink augmentation.

Estrogenic effects in the influents and effluents of the drinking water treatment plants - Yan-You Gou; Susana Lin; Danielle E. Que; Lemmuel L. Tayo; Ding-Yan Lin; Kuan-Chung Chen; Fu-An Chen; Pen-Chi Chiang; Gen-Shuh Wang; Yi-Chyuan Hsu; Kuo Pin Chuang; Chun-Yu Chuang; et al. (Environmental Science and Pollution Research, 2016)

An AhR-Luciferase Adenovirus Infection System for Rapid Screening of Dioxins in Soils - Cherng-Gueih Shy; How-Ran Chao; Ding-Yan Lin; Yan-You Gou; Chun-Yu Chuang; Kuo Pin Chuang; Chih-Cheng Chen; Yung-Chun Hsiao; Fu-An Chen (Bulletin of Environmental Contamination and Toxicology, 2016)

A simple and rapid approach to manipulate pseudorabies virus genome by CRISPR/Cas9 system - Aotian Xu; Chao Qin; Yue Lang; Mingyue Wang; Mengyang Lin; Chuang Li; Rui Zhang; Jun Tang (Biotechnology Letters, 2015)

EGFR mediates docetaxel resistance in human castration-resistant prostate cancer through the Akt-dependent expression of ABCB1 (MDR1) - Tzyh-Chyuan Hour; Shiu-Dong Chung; Wang-Yi Kang; Ying-Chu Lin; Shu-Ju Chuang; A-Mei Huang; Wen-Jeng Wu; Shu-Pin Huang; Chao-Yuan Huang; Yeong-Shiau Pu (Archives of Toxicology, 2015)

The development of stream temperature model in a mountainous river of Taiwan - Ching-Pin Tung; Tsung-Yu Lee; Jr-Chuang Huang; Po-Wen Perng; Shih-Ji Kao; Lin-Yen Liao (Environmental Monitoring and Assessment, 2014)

Antidepressant-like effects of the phosphodiesterase-4 inhibitor etazolate and phosphodiesterase-5 inhibitor sildenafil via cyclic AMP or cyclic GMP signaling in mice - Chuang Wang; Jianrui Zhang; Yang Lu; Peipei Lin; Tonghe Pan; Xin Zhao; Aiming Liu; Qinwen Wang; Wenhua Zhou; Han-Ting Zhang (Metabolic Brain Disease, 2014)

Novel quasi-subgenotype D2 of hepatitis B virus identified in Taiwanese aborigines - Huy Tran; Ming-Lung Yu; Chia-Yen Dai; I-Ling Lin; Ming-Lun Yeh; Wan-Long Chuang; Kenji Abe (Virus Genes, 2014)

SPIN: A Method of Skeleton-Based Polarity Identification for Neurons - Yi-Hsuan Lee; Yen-Nan Lin; Chao-Chun Chuang; Chung-Chuan Lo (Neuroinformatics, 2014)

BDNF and Exercise Enhance Neuronal DNA Repair by Stimulating CREB-Mediated Production of Apurinic/Apyrimidinic Endonuclease 1 - Jenq-Lin Yang; Yu-Ting Lin; Pei-Chin Chuang; Vilhelm A. Bohr; Mark P. Mattson (NeuroMolecular Medicine, 2014)

Trends in the susceptibility of methicillin-resistant Staphylococcus aureus to nine antimicrobial agents, including ceftobiprole, nemonoxacin, and tyrothricin: results from the Tigecycline In Vitro Surveillance in Taiwan (TIST) study, 2006–2010 - Y.-H. Chen; C.-Y. Liu; W.-C. Ko; C.-H. Liao; P.-L. Lu; C.-H. Huang; C.-T. Lu; Y.-C. Chuang; S.-M. Tsao; Y.-S. Chen; Y.-C. Liu; W.-Y. Chen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Identification of critical amino acid residues for chloride binding of Bacillus licheniformis trehalose-6-phosphate hydrolase - Ping-Lin Ong; Tzu-Ting Chuang; Tzu-Fan Wang; Long-Liu Lin (Biologia, 2014)

Cochlear Inner Hair Cell Ribbon Synapse is the Primary Target of Ototoxic Aminoglycoside Stimuli - Ke Liu; Xuejun Jiang; Chuang Shi; Lei Shi; Bo Yang; Lin Shi; Yice Xu; Weiyan Yang; Shiming Yang (Molecular Neurobiology, 2013)

Bird species migration ratio in East Asia, Australia, and surrounding islands - Yiliang Kuo; Da-Li Lin; Fu-Man Chuang; Pei-Fen Lee; Tzung-Su Ding (The Science of Nature, 2013)

Associations of T helper 1, 2, 17 and regulatory T lymphocytes with mortality in severe sepsis - Huang-Pin Wu; Kong Chung; Chun-Yao Lin; Bor-Yiing Jiang; Duen-Yau Chuang; Yu-Chih Liu (Inflammation Research, 2013)

Particle swarm optimization algorithm for analyzing SNP–SNP interaction of renin-angiotensin system genes against hypertension - Shyh-Jong Wu; Li-Yeh Chuang; Yu-Da Lin; Wen-Hsien Ho; Fu-Tien Chiang; Cheng-Hong Yang; Hsueh-Wei Chang (Molecular Biology Reports, 2013)

Application of a web-based remote agro-ecological monitoring system for observing spatial distribution and dynamics of Bactrocera dorsalis in fruit orchards - Joe-Air Jiang; Tzu-Shiang Lin; En-Cheng Yang; Chwan-Lu Tseng; Chia-Pang Chen; Chung-Wei Yen; Xiang-Yao Zheng; Chun-Yi Liu; Ren-Hau Liu; Yu-Fan Chen; Wan-Yi Chang; Cheng-Long Chuang (Precision Agriculture, 2013)

Understanding the trends in torsional effects in asymmetric-plan buildings - Jui-Liang Lin; Keh-Chyuan Tsai; Ming-Chieh Chuang (Bulletin of Earthquake Engineering, 2012)

Identification of furo[3′, 2′:3,4]naphtho[1,2-d]imidazole derivatives as orally active and selective inhibitors of microsomal prostaglandin E2 synthase-1 (mPGES-1) - Chih-Hua Tseng; Cherng-Chyi Tzeng; Pin-Keng Shih; Chia-Ning Yang; You-Chung Chuang; Shin-I Peng; Chang-Sheng Lin; Jih-Pyang Wang; Chih-Mei Cheng; Yeh-Long Chen (Molecular Diversity, 2012)

Preferential involvement of mitochondria in Toll-like receptor 3 agonist-induced neuroblastoma cell apoptosis, but not in inhibition of cell growth - Jiin-Haur Chuang; Tsu-Kung Lin; Ming-Hong Tai; Chia-Wei Liou; Sheng-Teng Huang; Chia-Ling Wu; Hung-Yi Lin; Pei-Wen Wang (Apoptosis, 2012)

Water Resources Flows Related to Urbanization in China: Challenges and Perspectives for Water Management and Urban Development - Chao Bao; Chuang-lin Fang (Water Resources Management, 2012)

Factors affecting grassland succession retardation in the Juifang area - Chao-Yuan Lin; Chin-Wei Chuang; Chang-Hai Chien (Natural Hazards, 2011)

Bacteremia caused by Brevundimonas species at a tertiary care hospital in Taiwan, 2000–2010 - M. R. Lee; Y. T. Huang; C. H. Liao; T. Y. Chuang; C. K. Lin; S. W. Lee; C. C. Lai; C. J. Yu; P. R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Prevention of cerebral ischemia-induced memory deficits by inhibition of phosphodiesterase-4 in rats - Ling-Xia Li; Yu-Fang Cheng; Huan-Bing Lin; Chuang Wang; Jiang-Ping Xu; Han-Ting Zhang (Metabolic Brain Disease, 2011)

Wake-promoting agent modafinil worsened attentional performance following REM sleep deprivation in a young-adult rat model of 5-choice serial reaction time task - Yia-Ping Liu; Che-Se Tung; Yu-Lung Lin; Chia-Hsin Chuang (Psychopharmacology, 2011)

SDF-1α inhibits hypoxia and serum deprivation-induced apoptosis in mesenchymal stem cells through PI3K/Akt and ERK1/2 signaling pathways - Qi Yin; Peifeng Jin; Xuebin Liu; Hua Wei; Xiaoming Lin; Chuang Chi; Yu Liu; Chengchao Sun; Yingjie Wei (Molecular Biology Reports, 2011)

Association between human papillomavirus and adenocarcinoma of rectum and recto-sigmoid junction: a cohort study of 10,612 women in Taiwan - Li-Chung Chuang; Hui-Chi Chen; San-Lin You; Ching-Yu Lin; Mei-Hung Pan; Yi-Chun Chou; Chang-Yao Hsieh; Chien-Jen Chen (Cancer Causes & Control, 2010)

Sex-specific genetic architecture of human fatness in Chinese: the SAPPHIRe Study - Y.-F. Chiu; L.-M. Chuang; H.-Y. Kao; K.-C. Shih; M.-W. Lin; W.-J. Lee; T. Quertermous; J. D. Curb; I. Chen; B. L. Rodriguez; C. A. Hsiung (Human Genetics, 2010)

Inhibition of phosphodiesterase-4 reverses memory deficits produced by Aβ25–35 or Aβ1–40 peptide in rats - Yu-Fang Cheng; Chuang Wang; Huan-Bing Lin; Yun-Feng Li; Ying Huang; Jiang-Ping Xu; Han-Ting Zhang (Psychopharmacology, 2010)

Positive culture for Klebsiella pneumoniae in relevant sputum samples as a predictor of rapidly fatal outcome in septic patients at medical intensive care units - T.-Y. Chuang; C.-J. Lin; T.-C. Chou; H.-H. Huang; S.-W. Lee; P.-R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Vegetation recovery and landscape change assessment at Chiufenershan landslide area caused by Chichi earthquake in central Taiwan - Chao-Yuan Lin; Chin-Wei Chuang; Wen-Tzu Lin; Wen-Chieh Chou (Natural Hazards, 2010)

Application and development of a decision-support system for assessing water shortage and allocation with climate change - Tzu-Ming Liu; C. P. Tung; K. Y. Ke; L. H. Chuang; C. Y. Lin (Paddy and Water Environment, 2009)

Indoor Air Distribution of Nitrogen Dioxide and Ozone in Urban Hospitals - Hong-Wen Chen; Chun-Yu Chuang; Heng-To Lin (Bulletin of Environmental Contamination and Toxicology, 2009)

Early transcriptional deregulation of hepatic mitochondrial biogenesis and its consequent effects on murine cholestatic liver injury - Mao-Meng Tiao; Tsu-Kung Lin; Cha-Wei Liou; Pei-Wen Wang; Jin-Bor Chen; Fang-Ying Kuo; Chao-Cheng Huang; Yao-Min Chou; Jiin-Haur Chuang (Apoptosis, 2009)

Effects of C-terminal amino acids truncation on enzyme properties of Aeromonas caviae D1 chitinase - Fu-Pang Lin; Hsu-Han Chuang; Yi-Hsuan Liu; Chia-Yu Hsieh; Pei-Wen Lin; Hsu-Yang Lin (Archives of Microbiology, 2009)

Group A streptococcal infection caused by emm1 strains among children in southern Taiwan - H.-C. Lin; S.-M. Wang; Y.-L. Lin; Y.-S. Lin; J.-J. Wu; W.-J. Chuang; M. T. Lin; C.-C. Liu (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Biochemical characterization of engineered amylopullulanase from Thermoanaerobacter ethanolicus 39E-implicating the non-necessity of its 100 C-terminal amino acid residues - Hsu-Yang Lin; Hsu-Han Chuang; Fu-Pang Lin (Extremophiles, 2008)

Solubilization of inorganic phosphates and plant growth promotion by Aspergillus niger - Chun-Chao Chuang; Yu-Lin Kuo; Chen-Ching Chao; Wei-Liang Chao (Biology and Fertility of Soils, 2007)

Management Implications to Water Resources Constraint Force on Socio-economic System in Rapid Urbanization: A Case Study of the Hexi Corridor, NW China - Chuang-lin Fang; Chao Bao; Jin-chuan Huang (Water Resources Management, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Solubilization of inorganic phosphates and plant growth promotion by Aspergillus niger - Chun-Chao Chuang; Yu-Lin Kuo; Chen-Ching Chao; Wei-Liang Chao (Biology and Fertility of Soils, 2007)

Streptococcal pyrogenic exotoxin B causes mitochondria damage to polymorphonuclear cells preventing phagocytosis of Group A streptococcus - Chuan Chiang-Ni; Chih-Hung Wang; Pei-Jane Tsai; Woei-Jer Chuang; Yee-Shin Lin; Ming-T. Lin; Ching-Chuan Liu; Jiunn-Jong Wu (Medical Microbiology and Immunology, 2006)

Expression studies of mutations underlying Taiwanese Hunter syndrome (mucopolysaccharidosis type II) - Jui-Hung Chang; Shuan-Pei Lin; Shu-Chuan Lin; Kai-Li Tseng; Chia-Ling Li; Chih-Kuang Chuang; Guey-Jen Lee-Chen (Human Genetics, 2005)

Evidence for the existence of some dissociation in an otherwise strong linkage disequilibrium between mitochondrial and chloroplastic genomes in Cyclobalanopsis glauca - T.‐P. Lin; W.‐J. Chuang; S. S. F. Huang; S.‐Y. Hwang (Molecular Ecology, 2003)
Variations in mitochondrial DNA in Cyclobalanopsis glauca (Thunb. ex Murray) Oerst. were studied in 140 trees from 32 populations collected from within the tree's natural range. By sequencing two mitochondrial DNA intron fragments ( nad 4/3 ‐nad 4/4r and nad 7/2 ‐nad 7/3r), we revealed a total of 1788 bp and five polymorphic sites which allowed us to distinguish six mitotypes. The mitochondrial DNA markers provided replicated data to support population phylogeographical scenarios suggested previously using chloroplastic DNA markers. The gene genealogical tree of mitochondrial DNA was partially congruent with the chloroplastic DNA tree owing to the slower mutation rate and different mutational direction. Significant linkage disequilibrium existed between the two organellar genomes. Further paring analyses between fragments synthesized using different primers, accompanied by exclusion of polymorphic sites, showed that the random association could be attributed specifically to one of the polymorphic sites of the pet G‐ trn P fragment of the chloroplastic genome, and the three polymorphic sites of the nad 4/3‐ nad 4/4r fragment of the mitochondrial genome. The former was inferred to derive from paternal leakage, and the latter from recurrent mutation. These polymorphic sites were also responsible for uncoupling of the combined gene tree of mitotype and chlorotype. In conclusion, specific fragments found in this study contribute to the incomplete congruence of the two organellar lineages that otherwise associate well phylogeographically.

Comparison of soil nitrogen mineralization and nitrification in a mixed grassland and forested ecosystem in central Taiwan - Jeffrey S. Owen; Ming Kuang Wang; Hai Lin Sun; Hen Biau King; Chung Ho Wang; Chin Fang Chuang (Plant and Soil, 2003)

Thoughts on constructing the demonstrating areas of the ecological rebuilding and economic sustainable development in Hexi Region - Chuang-lin Fang; Jin-chuan Huang; Yan-sui Liu (Chinese Geographical Science, 2002)

High incidence of JC viruria in JC-seropositive older individuals - Han Chang; Meilin Wang; Rong-Tai Tsai; Hui-Sheng Lin; Jin-Shue Huan; Wen-Chuang Wang; Deching Chang (Journal of NeuroVirology, 2002)

Water resources optimization and eco-environmental protection in Qaidam Basin - Fang Chuang-lin; Bao Chao (Journal of Geographical Sciences, 2001)

Envelope gene sequences of human T-lymphotropic virus type I in Taiwan - M. T. Lin; Y. C. Chen; P. J. Chen; Y. C. Yang; J. L. Tang; J. M. Wu; S. E. Chuang; C. S. Yang (Archives of Virology, 1996)